Hollow particles, method for producing hollow particles, resin composition, resin structure, and method for producing resin structure

By using a resin containing (meth)acryloyl polymerization and urethane bond/urea bond to form hollow particles of the shell, the problem of reducing pressure resistance at high temperature is solved, and better pressure resistance and shape uniformity are achieved.

CN119923419APending Publication Date: 2025-05-02ZEON CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380067009.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The pressure resistance of the conventional hollow particles is easily reduced at high temperatures, especially particles with polyurethane resin or polyurea resin shells, and particles with acrylic resin shells are insufficiently brittle and pressure resistance are insufficient.

Method used

The shell is formed using a structure composed of (meth)acryloyl group polymerization and at least one selected from the group consisting of a urethane bond and a urea bond, and hollow particles having an average circularity of 0.90 or more and a particle size distribution of D90/D50 is 1.70 or less.

Benefits of technology

The pressure resistance of hollow particles is significantly improved at high temperatures, ensuring their elasticity and strength under high temperature conditions, and avoiding the reduction of shell rigidity and shape uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005317026780000461
    Figure BDA0005317026780000461
  • Figure BDA0005317026780000471
    Figure BDA0005317026780000471
  • Figure HDA0005317026790000011
    Figure HDA0005317026790000011
Patent Text Reader

Abstract

Provided is a hollow particle in which a decrease in pressure resistance at high temperatures is suppressed. A hollow particle having a shell containing a resin and a hollow portion surrounded by the shell, the resin including a structure obtained by polymerizing a (meth) acryloyl group and at least one selected from the group consisting of urethane bonds and urea bonds, the hollow particle having an average circularity of 0.90 or more, when the volume-based cumulative 50% particle diameter of the hollow particles is D50 and the volume-based cumulative 90% particle diameter of the hollow particles is D90, the ratio (D90 / D50) of D90 to D50 is 1.70 or less, and the breaking strength when the hollow particles are compressed using a minute compression tester under the conditions of 150 DEG C, a maximum crushing test force of 2000 mN, and a load rate of 0.0466 mN / s is 5.0 MPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to hollow particles and a method for producing the same, as well as a resin composition and a resin structure containing the hollow particles and a method for producing the same. Background Art

[0002] Hollow particles have cavities inside the particles. Therefore, they are added to resins, coatings, or various molded bodies for the purpose of weight reduction, heat insulation, and low dielectric constant. Their applications cover a wide range of fields such as automobiles, bicycles, aviation, electrical, electronics, construction, home appliances, containers, stationery, tools, and shoes.

[0003] As a material forming the shell of the hollow particles, resins such as vinyl resins, acrylic resins, polyurethane resins, polyurea resins, and melamine resins, and inorganic materials such as silica, etc. can be used.

[0004] Among hollow particles having a shell containing a resin as a main component, i.e., hollow resin particles, hollow particles having a shell of a polyurethane resin or a polyurea resin are used for various purposes due to their excellent heat resistance and flexibility (e.g., Patent Documents 1 and 2).

[0005] Furthermore, Patent Document 3 describes hollow particles having a shell of an acrylic resin obtained using a trifunctional or higher-functional monomer containing a (meth)acryloyloxy group.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: International Publication No. 2019 / 181988.

[0009] Patent document 2: Japanese Patent Application Publication No. 2022-117594.

[0010] Patent document 3: Japanese Patent Application Publication No. 2020-033503. Summary of the invention

[0011] Problem that the invention aims to solve

[0012] However, conventional hollow particles having a shell of polyurethane resin or polyurea resin are easily deformed at high temperatures and are therefore difficult to use in applications that are subjected to external forces at high temperatures, such as when added to a resin for injection molding. On the other hand, hollow particles having a shell of acrylic resin are brittle and therefore have insufficient pressure resistance.

[0013] An object of the present invention is to provide hollow particles in which a decrease in pressure resistance at high temperatures is suppressed, and to provide a method for producing the hollow particles, a resin composition and a resin structure containing the hollow particles, and a method for producing the same.

[0014] Solutions for solving problems

[0015] The present inventors have discovered that hollow particles having a structure formed by polymerizing a (meth)acryloyl group and a resin selected from at least one of a urethane bond and a urea bond to form a shell, and having an average circularity of 0.90 or more and a particle size distribution D90 / D50 of 1.70 or less on a volume basis have excellent pressure resistance even at high temperatures, thereby completing the present invention.

[0016] The present invention provides a hollow particle having a shell made of a resin and a hollow part surrounded by the shell.

[0017] The resin comprises a structure formed by polymerization of (meth)acryloyl groups and at least one selected from urethane bonds and urea bonds,

[0018] The average circularity of the hollow particles is 0.90 or more.

[0019] When the volume-based cumulative 50% particle size of the hollow particles is D50 and the volume-based cumulative 90% particle size of the hollow particles is D90, a ratio of D90 to D50 (D90 / D50) is 1.70 or less,

[0020] When the hollow particles are compressed using a micro compression tester at 150° C., a maximum crushing test force of 2000 mN, and a load speed of 0.0466 mN / s, the breaking strength is 5.0 MPa or more.

[0021] In the hollow particles of the present invention, it is preferred that in an infrared absorption spectrum obtained by measuring the hollow particles by ATR-FTIR, the wavelength of 1500 to 1550 cm -1 The maximum peak absorbance A1 in the range of 1700-1750cm -1 The ratio (A1 / A2) of the absorbance A2 of the maximum peak in the range is greater than or equal to 0.1 and less than or equal to 0.5.

[0022] In the hollow particles of the present invention, the urea bond is preferably a urea bond generated by a reaction between a polyamine and an isocyanate group-containing compound.

[0023] In the hollow particles of the present invention, it is preferred that: the above-mentioned carbamate bond is a carbamate bond generated by the reaction of at least one active hydrogen compound selected from hydroxyl-containing compounds and epoxy-containing compounds with an isocyanate-containing compound, the above-mentioned hydroxyl-containing compound is at least one selected from polyester polyols, polyether polyols, aliphatic polyols, (meth)acrylic polymer polyols and hydroxyl-containing (meth)acrylates, and the above-mentioned epoxy-containing compound is a polycyclic epoxy compound.

[0024] In the hollow particles of the present invention, the porosity is preferably 60% or more and 85% or less.

[0025] The present invention provides a method for producing hollow particles, the method comprising:

[0026] A step of preparing a mixed solution comprising a shell raw material, a hydrophobic solvent, a dispersion stabilizer and an aqueous medium;

[0027] A step of suspending the mixed solution to prepare a suspension in which droplets of a shell raw material composition containing the shell raw material and the hydrophobic solvent are dispersed in the aqueous medium;

[0028] a step of forming precursor particles by polymerizing the shell raw material, the precursor particles having a shell made of a resin and a hollow portion surrounded by the shell and filled with the hydrophobic solvent; and

[0029] a step of removing the hydrophobic solvent from the precursor particles,

[0030] The shell raw material comprises at least one selected from the following (i), (ii) and (iii):

[0031] (i) a mixture of compounds, which is a mixture of an isocyanate group-containing compound and an active hydrogen compound, wherein at least one of the isocyanate group-containing compound and the active hydrogen compound contains a (meth)acryloyl group, and the active hydrogen compound is at least one selected from an amino group-containing compound, a hydroxyl group-containing compound, and an epoxy group-containing compound,

[0032] The mixture of the above compounds satisfies at least one of the following conditions: the above isocyanate group-containing compound contains two or more isocyanate groups in one molecule, or the above active hydrogen compound contains two or more at least one selected from amino, hydroxyl and epoxy groups in one molecule;

[0033] (ii) at least one selected from urethane bond-containing (meth)acrylates and urea bond-containing (meth)acrylates; and

[0034] (iii) a mixture of compounds, which is a mixture of an isocyanate group-containing compound, an active hydrogen compound and a (meth)acryloyl group-containing compound, wherein the active hydrogen compound is at least one selected from an amino group-containing compound, a hydroxyl group-containing compound and an epoxy group-containing compound,

[0035] In the polymerization of the shell raw material, at least one of a reaction between an isocyanate group and at least one selected from an amino group, a hydroxyl group, and an epoxy group, and a radical polymerization reaction of a (meth)acryloyl group proceeds.

[0036] The present invention provides a resin composition comprising the hollow particles of the present invention and a matrix resin.

[0037] The present invention provides a resin structure comprising the hollow particles of the present invention and a matrix resin.

[0038] The present invention further provides a method for producing a resin structure, comprising: preparing a resin composition containing the hollow particles of the present invention, a matrix resin, and a curing agent; and curing the resin composition.

[0039] Effects of the Invention

[0040] As described above, according to the present invention, hollow particles having reduced pressure resistance at high temperatures can be provided, and further the present invention provides a method for producing the hollow particles, a resin composition and a resin structure containing the hollow particles, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a diagram for explaining an example of the method for producing hollow particles of the present invention. DETAILED DESCRIPTION

[0042] The hollow particles of the present invention are characterized by having a shell composed of a resin and a hollow portion surrounded by the shell.

[0043] The resin comprises a structure formed by polymerization of (meth)acryloyl groups and at least one selected from urethane bonds and urea bonds,

[0044] The average circularity of the hollow particles is 0.90 or more.

[0045] When the volume-based cumulative 50% particle size of the hollow particles is D50 and the volume-based cumulative 90% particle size of the hollow particles is D90, a ratio of D90 to D50 (D90 / D50) is 1.70 or less,

[0046] When the hollow particles are compressed using a micro compression tester at 150° C., a maximum crushing test force of 2000 mN, and a load speed of 0.0466 mN / s, the breaking strength is 5.0 MPa or more.

[0047] The urea bond is a structure represented by -NH-CO-NH-, which is formed by the reaction of an isocyanate group (-NCO) with an amino group (-NH 2 ) is formed by the reaction.

[0048] The carbamate bond is a structure represented by -NH-CO-O- or -O-CO-NH-, and is formed by, for example, the reaction of an isocyanate group (-NCO) and a hydroxyl group (-OH). Since the epoxy group is ring-opened to become a hydroxyl group by contact with an acid or a base, the carbamate bond can also be formed by reacting an isocyanate group (-NCO) with an epoxy group in an acidic or alkaline state. In addition, in the reaction of an isocyanate group and an epoxy group, an oxazolidinone ring is sometimes formed.

[0049] Additionally, when a urethane bond reacts with an isocyanate group, an allophanate bond (-NH-CO-N-CO-O-) is formed.

[0050] Hollow particles have a cavity inside and are composed of a thin-walled shell. Therefore, compared with resin particles filled with resin inside, hollow particles tend to be easily deformed or broken when subjected to external force, that is, they have poor pressure resistance. The pressure resistance of conventional hollow particles with a shell of polyurethane resin or polyurea resin is easily reduced at high temperatures. It is inferred that this is because the crosslinking density of the resin forming the shell is insufficient, and the shell is easily softened or thermally decomposed at high temperatures, resulting in a decrease in the rigidity of the shell at high temperatures. In addition, in the present invention, high temperature can refer to an environment of 150°C to 300°C.

[0051] In contrast, the hollow particles of the present invention have a structure formed by polymerization of (meth)acryloyl groups and at least one selected from urethane bonds and urea bonds, and the average circularity of the particles is greater than 0.90, and D90 / D50 is less than 1.70, thereby having elasticity and strength superior to those of conventional hollow particles, and the elasticity and strength are easily maintained even at high temperatures, thereby exhibiting excellent pressure resistance even at high temperatures.

[0052] At least one selected from the group consisting of a urethane bond and a urea bond has a structure with excellent flexibility and forms hydrogen bonds in the resin, thereby imparting flexibility to the shell and increasing the rigidity of the shell by the formation of hydrogen bonds. The structure formed by the polymerization of the (meth)acryloyl group has high rigidity, thereby further imparting rigidity to the shell.

[0053] In addition, the average circularity of the hollow particles of the present invention is more than 0.90, and D90 / D50 is less than 1.70, that is, the uniformity of the shape and size of the particles is sufficiently high. The hollow particles with low average circularity are considered to be deformed due to the polymerization reaction of the raw materials not being fully carried out, and the hollow particles with large D90 / D50 are considered to be coarse particles produced due to the reaction of the particles with each other. It can be inferred that in the hollow particles of the present invention, the reason that the average circularity is more than 0.90 and D90 / D50 is less than 1.70 is considered to be because the polymerization reaction of the raw materials is fully carried out in the shell, so that the crosslinking density of the shell of the hollow particles of the present invention is sufficiently high.

[0054] Furthermore, as described above, particles with high uniformity in shape and size are more likely to receive external force uniformly, so that the elasticity and strength of each particle are effectively exerted, resulting in further improvement in pressure resistance.

[0055] Then, it can be inferred that since the structure formed by the polymerization of (meth)acryloyl groups maintains the cross-linked structure of the resin and the shape of the particles even at high temperatures, the decrease in rigidity and uniformity of the shell of the hollow particles of the present invention at high temperatures is suppressed, and excellent pressure resistance is maintained even at high temperatures.

[0056] It can be inferred that the hollow particles of the present invention have excellent pressure resistance due to the synergistic effect of the structure formed by polymerization of (meth)acryloyl groups and at least one selected from urethane bonds and urea bonds, the sufficiently high crosslinking density of the shell, and the excellent uniformity of the shape and size of the particles. The crosslinking structure of the resin forming the shell and the shape of the particles are easily maintained even at high temperatures, thereby achieving excellent pressure resistance.

[0057] Hereinafter, after describing an example of a method for producing the hollow particles of the present invention, the hollow particles of the present invention will be described in further detail.

[0058] In addition, in the present invention, "to" in a numerical range means that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0059] 1. Method for manufacturing hollow particles

[0060] The hollow particles of the present invention are typically produced by a production method described below based on a suspension polymerization method.

[0061] As a method for producing the hollow particles of the present invention, for example, there can be mentioned a method having the following steps:

[0062] A step of preparing a mixed solution comprising a shell raw material, a hydrophobic solvent, a dispersion stabilizer and an aqueous medium;

[0063] A step of suspending the mixed solution to prepare a suspension in which droplets of a shell raw material composition containing the shell raw material and the hydrophobic solvent are dispersed in the aqueous medium;

[0064] a step of forming precursor particles by polymerizing the shell raw material, the precursor particles having a shell made of a resin and a hollow portion surrounded by the shell and filled with the hydrophobic solvent; and

[0065] A step of removing the hydrophobic solvent from the precursor particles.

[0066] In the present invention, the raw material of the resin contained in the shell is referred to as "shell raw material", and the polymerization initiator is not contained in the shell raw material. In the present invention, "shell raw material composition" means a composition containing the shell raw material.

[0067] In the present invention, "polymerization of the shell material" may be any reaction in which compounds contained in the shell material are bonded to each other via covalent bonds, and may be any of a reaction of an isocyanate group-containing compound and an active hydrogen compound, a polymerization reaction of a (meth)acryloyl group, and a combination thereof.

[0068] In the present invention, hollow particles whose hollow parts are filled with a hydrophobic solvent are sometimes considered to be intermediates of hollow particles whose hollow parts are filled with a gas, and are referred to as “precursor particles.” In the present invention, a “precursor composition” refers to a composition containing precursor particles.

[0069] In the above-mentioned production method, a suspension is prepared by suspending a mixed liquid containing a shell raw material, a hydrophobic solvent, a dispersion stabilizer and an aqueous medium, wherein the suspension is formed by dispersing droplets of a shell raw material composition having a distribution structure in which the shell raw material and the hydrophobic solvent are phase-separated, the shell raw material is preferentially present on the surface side, and the hydrophobic solvent is preferentially present in the center. When the suspension is supplied to a polymerization reaction, a resin (polymer) begins to precipitate on the surface of the droplets of the shell raw material composition, and the polymerization reaction is further performed, whereby the surface of the droplets is solidified to form a shell, and a hollow particle having a hollow part filled with a hydrophobic solvent is obtained.

[0070] In the method using the interfacial polymerization method described in Patent Document 2, the reaction between the isocyanate group-containing compound and water easily occurs, so it is difficult to increase the crosslinking density of the resin forming the shell. In the present invention, by using the method based on the suspension polymerization method as described above, a shell with a sufficiently high crosslinking density can be formed, and hollow particles whose pressure resistance is not easily reduced at high temperatures can be prepared.

[0071] The above-mentioned manufacturing method includes the steps of preparing a mixed solution, preparing a suspension, polymerizing the shell raw material, and removing the solvent contained in the particles, and may further include steps other than these. In addition, as long as it is technically possible, two or more of the above-mentioned steps and other additional steps can be carried out simultaneously as one step, or the order can be reversed. For example, the materials for preparing the mixed solution can be added while the suspension is carried out, so that the preparation of the mixed solution and the suspension can be carried out simultaneously in one step.

[0072] As a preferred example of the method for producing hollow particles of the present invention, there can be mentioned a method including the following steps.

[0073] (1) Mixed solution preparation process

[0074] A step of preparing a mixed solution comprising a shell raw material, a hydrophobic solvent, a dispersion stabilizer and an aqueous medium;

[0075] (2) Suspension process

[0076] A step of suspending the mixed solution to prepare a suspension in which droplets of a shell raw material composition containing a shell raw material and a hydrophobic solvent are dispersed in an aqueous medium;

[0077] (3) Polymerization process

[0078] a step of forming precursor particles by polymerizing the shell raw material, the precursor particles having a shell made of a resin and a hollow portion surrounded by the shell and filled with the hydrophobic solvent; and

[0079] (4) Solvent Removal Process

[0080] A step of removing the hydrophobic solvent from the precursor particles to obtain hollow particles.

[0081] Figure 1 This is a schematic diagram showing an example of the production method of the present invention. Figure 1 (1) to (4) in the figure correspond to the above steps (1) to (4). The white arrows between the figures indicate the order of the steps. Figure 1 The schematic diagrams are only for explanation, and the manufacturing method of the present invention is not limited to the manufacturing method shown in the figures. In addition, the structure, size and shape of the materials used in the manufacturing method of the present invention are not limited to the structure, size and shape of the various materials in these figures.

[0082] Figure 1 (1) is a cross-sectional schematic diagram showing an embodiment of a mixed solution in the mixed solution preparation process. As shown in this figure, the mixed solution includes an aqueous medium 1 and a low-polarity material 2 dispersed in the aqueous medium 1. Here, the low-polarity material 2 refers to a material with low polarity and difficult to mix with the aqueous medium 1. In the present invention, the low-polarity material 2 includes a shell raw material and a hydrophobic solvent.

[0083] Figure 1 (2) is a cross-sectional schematic diagram showing an embodiment of a suspension in the suspension process. The suspension includes an aqueous medium 1 and droplets 3 of a shell raw material composition dispersed in the aqueous medium 1. The droplets 3 of the shell raw material composition include a shell raw material and a hydrophobic solvent, but the distribution in the droplets is uneven. The droplets 3 of the shell raw material composition have the following structure: the hydrophobic solvent 4a and the material 4b other than the hydrophobic solvent containing the shell raw material are phase-separated, the hydrophobic solvent 4a tends to exist in the center, the material 4b other than the hydrophobic solvent tends to exist on the surface side, and a dispersion stabilizer (not shown) is attached to the surface.

[0084] Figure 1 (3) is a schematic cross-sectional view showing an embodiment of a precursor particle obtained by a polymerization process, wherein the hollow part is filled with a hydrophobic solvent. The precursor particle 5 has a shell 6 containing a resin and a hollow part filled with a hydrophobic solvent 4a. The shell 6 forming the outer surface of the precursor particle 5 is formed by polymerization of the shell raw material contained in the droplets 3 of the shell raw material composition. Figure 1 In (3), the precursor particles 5 are dispersed in the aqueous medium 1 .

[0085] Figure 1 (4) is a schematic cross-sectional view showing one embodiment of the hollow particles after the solvent removal step. Figure 1 (4) shows that from the above Figure 1 The state after removing the aqueous medium 1 and the hydrophobic solvent 4a from the state (3) of the precursor particles. By removing the hydrophobic solvent contained in the precursor particles, hollow particles 10 having a hollow part 7 filled with gas inside the shell 6 can be obtained.

[0086] Hereinafter, the above four steps and other steps will be described in sequence.

[0087] (1) Mixed solution preparation process

[0088] This step is a step of preparing a mixed solution containing a shell raw material, a hydrophobic solvent, a dispersion stabilizer, and an aqueous medium. When the shell raw material contains a (meth)acryloyl group-containing compound, the mixed solution preferably further contains a polymerization initiator.

[0089] The mixed liquid may further contain other materials within a range not impairing the effects of the present invention.

[0090] The materials of the mixed solution are described in the order of (A) shell raw material, (B) hydrophobic solvent, (C) polymerization initiator, (D) dispersion stabilizer, and (E) aqueous medium.

[0091] (A) Shell material

[0092] The shell raw material is not particularly limited as long as it can form a resin containing a structure formed by polymerization of a (meth)acryloyl group and at least one selected from a urethane bond and a urea bond. For example, a shell raw material containing at least one selected from the following (i), (ii) and (iii) can be preferably used.

[0093] (i) A mixture of compounds, which is a mixture of an isocyanate group-containing compound and an active hydrogen compound, at least one of which contains a (meth)acryloyl group, the active hydrogen compound is at least one selected from an amino group-containing compound, a hydroxyl group-containing compound, and an epoxy group-containing compound, and the mixture of compounds satisfies at least one of the following: the isocyanate group-containing compound contains two or more isocyanate groups in one molecule, or the active hydrogen compound contains two or more at least one selected from an amino group, a hydroxyl group, and an epoxy group in one molecule.

[0094] (ii) at least one selected from the group consisting of urethane bond-containing (meth)acrylates and urea bond-containing (meth)acrylates.

[0095] (iii) A mixture of compounds, which is a mixture of an isocyanate group-containing compound, an active hydrogen compound and a (meth)acryloyl group-containing compound, wherein the active hydrogen compound is at least one selected from an amino group-containing compound, a hydroxyl group-containing compound and an epoxy group-containing compound.

[0096] The shell raw material may contain only one selected from (i), (ii) and (iii) above, or may contain two or more in combination. For example, the shell raw material may contain a mixture of the compounds of (i) above and the compound of (ii) above in combination.

[0097] From the viewpoint of easily improving the pressure resistance of the hollow particles and easily suppressing a decrease in pressure resistance at high temperatures, the shell raw material preferably contains at least one of (i) and (ii), and is particularly preferably a mixture containing the compound of (i).

[0098] In the present invention, the isocyanate group-containing compound refers to a compound containing one or more isocyanate groups in one molecule, wherein a compound containing two or more isocyanate groups in one molecule is referred to as a polyisocyanate. In addition, the isocyanate group-containing compound also includes a compound that can desorb ketones and the like by reacting the isocyanate group with ketones, alcohols, oximes, etc. to reduce the reactivity of the isocyanate group.

[0099] The amino group-containing compound refers to a compound containing one or more amino groups in one molecule, and a compound containing two or more amino groups in one molecule is called a polyamine. The amino group contained in the amino group-containing compound is an amino group that reacts with an isocyanate group to form a urea bond, and is preferably a primary amino group or an aliphatic secondary amino group.

[0100] The hydroxyl group-containing compound refers to a compound containing one or more hydroxyl groups in one molecule, and a compound containing two or more hydroxyl groups in one molecule is referred to as a polyol. The hydroxyl group contained in the hydroxyl group-containing compound reacts with an isocyanate group to form a urethane bond.

[0101] An epoxy-containing compound refers to a compound containing one or more epoxy groups in one molecule, and a compound containing two or more epoxy groups in one molecule is called a polyepoxy compound. The epoxy group contained in the epoxy-containing compound is ring-opened to a hydroxyl group by contact with an acid or a base, and the hydroxyl group reacts with an isocyanate group to form a urethane bond.

[0102] In the present invention, the (meth)acryloyl-containing compound refers to a compound containing one or more (meth)acryloyl groups in one molecule. Among them, (meth)acrylate is sometimes referred to as (meth)acrylate, and the polymer obtained by the polymerization reaction of (meth)acryloyl is sometimes referred to as (meth)acrylic polymer. In addition, a (meth)acrylate containing only one (meth)acryloyl group in one molecule is referred to as a monofunctional (meth)acrylate, and a (meth)acrylate containing two or more (meth)acryloyl groups in one molecule is referred to as a multifunctional (meth)acrylate.

[0103] In the present invention, (meth)acrylate means at least one selected from acrylate and methacrylate, (meth)acrylic acid means at least one selected from acrylic acid and methacrylic acid, and (meth)acryloyl means at least one selected from acryloyl and methacryloyl. That is, the structure formed by polymerizing (meth)acryloyl means the structure formed by polymerizing at least one selected from acryloyl and methacryloyl.

[0104] Examples of the mixture of the compounds (i) include:

[0105] (i-1) a mixture of an isocyanate group-containing (meth)acrylate containing one isocyanate group in one molecule and at least one active hydrogen compound selected from the group consisting of polyamines, polyols and polyepoxides;

[0106] (i-2) a mixture of an isocyanate group-containing (meth)acrylate containing one isocyanate group in one molecule and a hydroxyl group-containing (meth)acrylate containing two or more hydroxyl groups in one molecule;

[0107] (i-3) a mixture of a polyisocyanate and at least one active hydrogen compound selected from an amino-containing (meth)acrylate containing one amino group in one molecule, a hydroxyl-containing (meth)acrylate containing one hydroxyl group in one molecule, and an epoxy-containing (meth)acrylate containing one epoxy group in one molecule; and

[0108] (I-4) A mixture of a polyisocyanate and a hydroxyl group-containing (meth)acrylate containing two or more hydroxyl groups in one molecule, and the like.

[0109] The (meth)acrylate such as the isocyanate group-containing (meth)acrylate used above is preferably a polyfunctional (meth)acrylate containing two or more (meth)acryloyl groups in one molecule, from the viewpoint of easily improving the pressure resistance of the hollow particles and easily suppressing a decrease in pressure resistance at high temperatures.

[0110] In addition, from the viewpoint of easily improving the pressure resistance of the hollow particles and easily obtaining hollow particles whose pressure resistance is not easily reduced at high temperatures, among the above (i-1) to (i-4), it is preferred to use an isocyanate group-containing multifunctional (meth)acrylate as the isocyanate group-containing (meth)acrylate in the above (i-1) and (i-2), and the above (i-3) and (i-4).

[0111] Specific examples of the compounds used in (i-1) to (i-4) are described below. In addition, the compounds described below can be used alone or in combination of two or more in a plurality of specific examples.

[0112] Examples of the isocyanate group-containing (meth)acrylate containing one isocyanate group in one molecule include isocyanate group-containing monofunctional (meth)acrylates such as 2-isocyanoethyl (meth)acrylate and 2-(2-(meth)acryloyloxyethyloxy)ethyl isocyanate; and isocyanate group-containing polyfunctional (meth)acrylates such as 1,1-(bisacryloyloxymethyl)ethyl isocyanate.

[0113] Examples of the polyisocyanate include aliphatic polyisocyanates such as ethylene diisocyanate, pentamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexane diisocyanate, dicyclohexylmethane diisocyanate, hydrogenated xylylene diisocyanate, and norbornene diisocyanate; and aromatic polyisocyanates such as phenylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, tetramethylxylene diisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, and carbodiimidized diphenylmethane polyisocyanate.

[0114] Examples of the amino group-containing (meth)acrylate containing one amino group in one molecule include amino group-containing monofunctional (meth)acrylates such as tert-butylaminoethyl (meth)acrylate and 2-aminoethyl (meth)acrylate.

[0115] Examples of the polyamine include aromatic polyamines, aliphatic polyamines, alicyclic polyamines, polyether amines, piperazine-based amines, and norbornane-based polyamines.

[0116] Examples of the aromatic polyamine include low molecular weight aromatic polyamines such as m-phenylenediamine, diethyltoluenediamine, 4,4′-diamino-3,3′-dichlorodiphenylmethane, and trimethylene-bis(4-aminobenzoate); and high molecular weight aromatic polyamines such as polytetramethylene oxide-diparaaminobenzoate.

[0117] Examples of the aliphatic polyamine include ethylenediamine, hexamethylenediamine, 1,5-diamino-2-methylpentane, and triethylenetetramine.

[0118] As alicyclic polyamine, isophoronediamine, 1, 3- bisaminomethylcyclohexane, etc. are mentioned, for example.

[0119] Examples of the piperazine-based amines include N-aminoethylpiperazine and the like.

[0120] Examples of the polyetheramine include polyoxyethylenediamine and O,O′-bis(2-aminopropyl)polyethylene glycol.

[0121] As a norbornane type polyamine, a norbornanediamine etc. are mentioned, for example.

[0122] As the polyamine, from the viewpoint of facilitating improvement of the pressure resistance of the hollow particles and facilitating suppression of reduction in pressure resistance at high temperatures, aliphatic polyamines are preferred, and alkyl polyamines having 2 to 6 carbon atoms are more preferred.

[0123] Examples of the hydroxyl group-containing (meth)acrylate containing one hydroxyl group in one molecule include hydroxyl group-containing monofunctional (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, hydroxycyclohexyl (meth)acrylate, 3-(meth)acryloyloxy-2-hydroxypropyl (meth)acrylate, and N-methylol (meth)acrylamide; and hydroxyl group-containing polyfunctional (meth)acrylates such as 2-hydroxy-1,3-dimethacryloyloxypropane, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, and sorbitol penta(meth)acrylate.

[0124] Examples of the hydroxyl-containing (meth)acrylate containing two or more hydroxyl groups in one molecule include hydroxyl-containing monofunctional (meth)acrylates such as pentaerythritol mono(meth)acrylate and dipentaerythritol mono(meth)acrylate; and hydroxyl-containing multifunctional (meth)acrylates such as pentaerythritol di(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, sorbitol tri(meth)acrylate, and sorbitol tetra(meth)acrylate.

[0125] Examples of the polyol include polyester polyol, polyether polyol, aliphatic polyol, (meth)acrylic polymer polyol, etc. The above-mentioned hydroxyl group-containing (meth)acrylate containing two or more hydroxyl groups in one molecule is also a polyol.

[0126] Examples of the polyester polyol include: condensation polyesters obtained by polycondensing one or more dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, sebacic acid, azelaic acid, and maleic acid with one or more diols such as ethylene glycol (EG), 1,3-propylene glycol, 1,4-butanediol (BD), 1,6-hexanediol, neopentyl glycol (NPG), 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,8-octanediol, 1,10-decanediol, and diethylene glycol, and ring-opening polymerized polyesters obtained by ring-opening addition polymerization of lactones such as ε-caprolactone and valerolactone using the above diols as polymerization initiator components of the polyester, etc. From the viewpoint of increasing the crosslinking density of the shell to easily increase the pressure resistance of the hollow particles and easily suppressing the decrease in pressure resistance at high temperatures, the polyester polyol preferably has a molecular weight within the range of 1000 to 3000.

[0127] Examples of polyether polyols include polyoxyalkylene polyols containing two or more oxyalkylene units and two or more hydroxyl groups in one molecule. Examples of polyoxyalkylene polyols include homopolymers of oxyalkylene polyols such as polyoxyethylene polyol, polyoxypropylene polyol, and polyoxytetramethylene glycol, copolymers of two or more oxyalkylene polyols, and copolymers obtained by addition polymerization of alkylene oxides and initiators such as alkylene glycols. Examples of copolymers of two or more oxyalkylene polyols include copolymers containing polymethylene oxide units represented by the following formula (1) and polyalkylene oxide units represented by the following formula (2), and having two or more hydroxyl groups at the ends.

[0128] -[(CH 2 ) m O]- (1)

[0129] -[(CXH) n O]- (2)

[0130] In the above formula (1), m is an integer of 2-10, preferably an integer of 3-6.

[0131] In the above formula (2), n is an integer of 3 to 10, preferably an integer of 3 to 6, at least one of the n Xs is an alkyl group, and the others are hydrogen atoms.

[0132] As the polyether polyol, a copolymer obtained by addition polymerization of an alkylene oxide and an alkylene glycol is preferred, especially from the viewpoint of increasing the crosslinking density of the shell to easily improve the pressure resistance of the hollow particles and easily suppressing the decrease in pressure resistance at high temperature. As the alkylene glycol, an alkylene glycol having 2 to 6 carbon atoms is preferred, and as the alkylene oxide, an alkylene oxide having 2 to 6 carbon atoms is preferred.

[0133] In the present invention, aliphatic polyol refers to a saturated aliphatic polyol. As aliphatic polyol, for example, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, MPD (3-methyl-1,5-pentanediol), MOD (2-methyl-1,8-octanediol), neopentyl glycol, glycerol, trimethylolpropane, pentaerythritol, etc. can be cited. As aliphatic polyol, especially from the viewpoint of increasing the crosslinking density of the shell and easily improving the pressure resistance of the hollow particles and easily suppressing the decrease in pressure resistance at high temperature, aliphatic polyols such as pentaerythritol and glycerol containing three or more hydroxyl groups in one molecule are preferred.

[0134] As the (meth)acrylic polymer polyol, for example, the homopolymer or copolymer of the above-mentioned hydroxyl-containing (meth)acrylate can be cited. From the viewpoint of increasing the crosslinking density of the shell to easily improve the pressure resistance of the hollow particles and easily suppressing the reduction of the pressure resistance at high temperature, as the (meth)acrylic polymer polyol, a (meth)acrylic polymer polyol with a weight average molecular weight in the range of 1000 to 20000 is preferred. In addition, as the hydroxyl-containing (meth)acrylate used in the synthesis of the (meth)acrylic polymer polyol, a hydroxyl-containing multifunctional (meth)acrylate is preferred.

[0135] Examples of epoxy group-containing (meth)acrylates containing one epoxy group in one molecule include epoxy group-containing monofunctional (meth)acrylates such as glycidyl (meth)acrylate, epoxycyclohexylmethyl (meth)acrylate, and mono(meth)acrylates of diglycidyl ether compounds such as bisphenol diglycidyl ether.

[0136] Examples of the polyvalent epoxy compound include glycidyl ether-type compounds such as bisphenol A diglycidyl ether, bisphenol A di-β-methyl glycidyl ether, bisphenol F diglycidyl ether, tetrahydroxyphenylmethane tetraglycidyl ether, resorcinol diglycidyl ether, brominated bisphenol A diglycidyl ether, chlorinated bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, diglycidyl ether of bisphenol A alkylene oxide adduct, novolac glycidyl ether, polyalkylene glycol diglycidyl ether, glycerol triglycidyl ether, and pentaerythritol diglycidyl ether; glycidyl ether / ester-type compounds such as p-hydroxybenzoic acid glycidyl ether / ester; diglycidyl phthalate, tetrahydrophthalic acid diglycidyl ether, and hexahydrophthalic acid diglycidyl ether. , diglycidyl acrylate, diglycidyl dimer acid diglycidyl ester type; glycidyl amine type such as glycidyl aniline, tetraglycidyl diaminodiphenylmethane, triglycidyl isocyanurate, aminophenol triglycidyl ester; linear aliphatic epoxy compounds such as epoxidized polybutadiene and epoxidized soybean oil; alicyclic epoxy compounds such as 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarboxylate, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, bis(3,4-epoxy-6-methylcyclohexylmethyl)adipate, vinyl cyclohexene diepoxide, dicyclopentadiene oxide, bis(2,3-epoxycyclopentyl) ether, and limonene dioxide.

[0137] As the polyvalent epoxy compound, a glycidyl ether type epoxy compound is preferred, and resorcinol diglycidyl ether is particularly preferred, from the viewpoint of increasing the crosslinking density of the shell to easily improve the pressure resistance of the hollow particles and easily suppressing a decrease in pressure resistance at high temperatures.

[0138] Commercially available products may be used as the polyvalent epoxy compound. Examples of commercially available products of the polyvalent epoxy compound include Denacol EX-810, 810P, 811, 850, 851, 821, 830, 832, 841, 861, 214, 920, 201, 201-IM, 211, 212, 212L, 252, 931, and 991L manufactured by Nagase ChemteX Co., Ltd.

[0139] The mixture of the compounds of (i) above may further contain a (meth)acryloyl-containing compound that does not contain any of an isocyanate group, an amino group, a hydroxyl group, and an epoxy group. Examples of such (meth)acryloyl-containing compounds include monofunctional (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetramethacrylate, and the like. Multifunctional (meth)acrylates such as alcohol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol poly(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and ethoxylated bisphenol A di(meth)acrylate; allyl (meth)acrylate, vinyl (meth)acrylate, etc.

[0140] In (ii) above, the urethane bond-containing (meth)acrylate refers to a compound containing a urethane bond and a (meth)acryloyl group in one molecule, and for example, an oligomer containing a polyurethane structure and at least one (meth)acryloyl group can be preferably used.

[0141] In the above (ii), the urea bond-containing (meth)acrylate refers to a compound containing a urea bond and a (meth)acryloyl group in one molecule, and for example, an oligomer containing a polyurea structure and at least one (meth)acryloyl group can be preferably used.

[0142] From the viewpoint of increasing the cross-linking density of the resin forming the shell and easily improving the pressure resistance of the hollow particles and easily suppressing the reduction of the pressure resistance at high temperature, urethane bond-containing (meth)acrylates and urea bond-containing (meth)acrylates are preferred. As urethane bond-containing (meth)acrylates and urea bond-containing (meth)acrylates, urethane bond-containing (meth)acrylates are preferred, and oligomers containing a polyurethane structure and at least one (meth)acryloyl group in one molecule are more preferred.

[0143] The urethane bond-containing (meth)acrylate and the urea bond-containing (meth)acrylate may be a synthetic product obtained by polymerizing desired monomers, or may be a commercially available product.

[0144] Examples of commercially available products of urethane bond-containing (meth)acrylates include EBECRYL 230, EBECRYL 270, EBECRYL 4858, EBECRYL 8402, EBECRYL 8804, EBECRYL 4513, EBECRYL 4738, EBECRYL 4740, EBECRYL 8465, EBECRYL 9260, EBECRYL 4666, EBECRYL 8210, EBECRYL 8606, EBECRYL 1290, EBECRYL 5129, EBECRYL 8301R, KRM 8200, EBECRYL 210, and EBECRYL 220 (Daicel-Allnex Co., Ltd.), Miramer PU 2100, Miramer WS 2600, and Miramer WS 4000 (Migen Co., Ltd.).

[0145] The above-mentioned (ii) may be a mixture containing a (meth)acryloyl group-containing compound that does not contain any of an isocyanate group, an amino group, a hydroxyl group, and an epoxy group. Specific examples of such a (meth)acryloyl group-containing compound are as described above.

[0146] As the isocyanate group-containing compound, amino group-containing compound, hydroxyl group-containing compound and epoxy group-containing compound used in the mixture of compounds in (iii), the polyisocyanate, polyamine, polyol and polyepoxy compound used in (i) can be preferably used. In (iii), the isocyanate group-containing compound and the active hydrogen compound may or may not have a (meth)acryloyl group.

[0147] Examples of the (meth)acryloyl group-containing compound used in the above-mentioned (iii) include the same compounds as the above-mentioned (meth)acryloyl group-containing compound not containing any of an isocyanate group, an amino group, a hydroxyl group and an epoxy group.

[0148] In the range that does not impair the effect of the present invention, the shell raw material may also contain a radical polymerizable compound that does not contain any of an isocyanate group, an amino group, a hydroxyl group, an epoxy group, and a (meth) acryloyl group, and contains a radical polymerizable group other than a (meth) acryloyl group. As the radical polymerizable compound, for example: hydrocarbon monomers such as aromatic vinyl monomers and diene monomers; allyl monomers such as diallyl phthalate; carboxylic acid vinyl ester monomers such as vinyl acetate; halogenated aromatic vinyl monomers such as halogenated styrenes; halogenated vinyl monomers such as vinyl chloride; vinylidene halide monomers such as vinylidene chloride; vinyl pyridine, etc. In addition, in the present invention, a compound composed of carbon and hydrogen and containing a vinyl group is referred to as a hydrocarbon monomer.

[0149] Examples of the aromatic vinyl monomer include aromatic divinyl monomers such as divinylbenzene, divinylbiphenyl and divinylnaphthalene; and aromatic monovinyl monomers such as styrene, vinyltoluene, α-methylstyrene, p-methylstyrene, ethylvinylbenzene, ethylvinylbiphenyl and ethylvinylnaphthalene.

[0150] Examples of the diene monomer include linear or branched dienes such as butadiene, isoprene, 2,3-dimethylbutadiene, pentadiene, and hexadiene; and alicyclic dienes such as dicyclopentadiene, cyclopentadiene, and ethylenetetracyclododecene.

[0151] Examples of the hydrocarbon monomer include linear or branched monoolefins such as ethylene, propylene, and butene; and alicyclic monoolefins such as vinylcyclohexane, norbornene, and tricyclododecene.

[0152] Among them, as the radical polymerizable compound, a hydrocarbon monomer is preferred, an aromatic vinyl monomer is more preferred, and an aromatic divinyl monomer is further preferred.

[0153] In the case where the resin forming the shell contains a urea bond, the urea bond is preferably a urea bond generated by a reaction of a polyamine and an isocyanate group-containing compound.

[0154] In the case where the resin forming the shell contains a urethane bond, the urethane bond is preferably a urethane bond generated by reacting at least one selected from polyester polyols, polyether polyols, aliphatic polyols, (meth)acrylic polymer polyols, hydroxyl group-containing (meth)acrylates and polycyclic epoxy compounds with an isocyanate group-containing compound.

[0155] This is because, by using at least one selected from polyamines, polyester polyols, polyether polyols, aliphatic polyols, (meth)acrylic polymer polyols, hydroxyl group-containing (meth)acrylates and polyvalent epoxy compounds as the active hydrogen compound, the pressure resistance of the hollow particles is improved, and there is a tendency that a decrease in pressure resistance at high temperatures is suppressed.

[0156] Among them, the urethane bond is more preferably a urethane bond generated by reaction of at least one active hydrogen compound selected from aliphatic polyols, (meth)acrylic polymer polyols, hydroxyl group-containing (meth)acrylates and polyvalent epoxy compounds with an isocyanate group-containing compound.

[0157] From the viewpoint of being particularly easy to increase the crosslink density of the resin forming the shell, the active hydrogen compound is preferably an aliphatic polyol and an aliphatic polyamine having a solubility of 0.1 to 700 g / L in water at 15°C and a molecular weight of 100 to 20,000, and at least one selected from polyester polyols, polyether polyols, (meth) acrylic polymer polyols, hydroxyl-containing (meth) acrylic esters, and polyvalent epoxy compounds. These active hydrogen compounds are easy to stay in the shell during the polymerization reaction, and the polymerization reaction in the shell can be fully carried out, so the crosslink density of the shell can be increased. In addition, by using these active hydrogen compounds, the reaction between particles is particularly suppressed, so the aggregation of hollow particles can be suppressed, the amount of coarse powder can be reduced, and D90 / D50 can be reduced in the obtained hollow particles.

[0158] From the viewpoint of increasing the crosslinking density of the shell to easily improve the pressure resistance of the hollow particles and to easily suppress the reduction in pressure resistance at high temperatures, the structural units derived from the isocyanate group-containing compound contained in the shell preferably include structural units derived from at least one selected from isocyanate group-containing (meth)acrylates and polyisocyanates, and more preferably include structural units derived from isocyanate group-containing multifunctional (meth)acrylates.

[0159] In the shell of the hollow particles of the present invention, relative to the total of 100 parts by mass of the structural units from the isocyanate group-containing compound and the structural units from the active hydrogen compound, the lower limit of the content of the structural units from the active hydrogen compound is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and the upper limit of the content of the structural units from the active hydrogen compound is preferably 70 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 50 parts by mass or less. When the proportion of the structural units from the active hydrogen compound is within the above range, the crosslinking density of the shell is easily increased, and therefore, the pressure resistance of the hollow particles is easily increased, and the pressure resistance is not easily reduced at high temperatures. In addition, when the proportion of the structural units from the active hydrogen compound is within the above range, deformation of the hollow particles is particularly difficult to occur, so the average circularity can be easily made to be 0.90 or more.

[0160] In addition, carbamate-containing (meth)acrylates are usually obtained by the reaction of isocyanate-containing compounds and hydroxyl-containing (meth)acrylates. Therefore, it can be considered that the structural unit from carbamate-containing (meth)acrylates is composed of the structural unit from the isocyanate-containing compound and the structural unit from the hydroxyl-containing (meth)acrylate. Urea-containing (meth)acrylates are usually obtained by the reaction of isocyanate-containing compounds and amino-containing (meth)acrylates, and therefore, it can be considered that the structural unit from carbamate-containing (meth)acrylates is composed of the structural unit from the isocyanate-containing compound and the structural unit from the amino-containing (meth)acrylate.

[0161] In addition, the content of each structural unit contained in the resin forming the shell can be obtained from the shell raw material used in the production.

[0162] In addition, the content of the structural unit derived from the active hydrogen compound is preferably 10% by mass or more, more preferably 15% by mass or more, as a lower limit, and preferably 70% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less, relative to 100% by mass of the resin, as an upper limit. When the content of the structural unit derived from the active hydrogen compound is within the above range, the crosslinking density of the shell is easily increased, and therefore, the pressure resistance of the hollow particles is easily improved, and the pressure resistance is not easily reduced at high temperatures.

[0163] In addition, 100% by mass of the resin and 100% by mass of the shell raw material are the same.

[0164] In addition, the content of the structural unit derived from the (meth) acryloyl compound is preferably 30% by mass or more, more preferably 40% by mass or more, and further preferably 50% by mass or more relative to 100% by mass of the resin. The upper limit is not particularly limited, and for example, it may be 90% by mass or less. When the content of the structural unit derived from the (meth) acryloyl compound is within the above range, the crosslinking density of the shell is easily increased, and therefore, the pressure resistance of the hollow particles is easily increased, and the pressure resistance is not easily reduced at high temperatures.

[0165] Here, the (meth)acryloyl group-containing compound includes the following compounds, namely, compounds containing functional groups other than (meth)acryloyl groups, such as isocyanate group-containing (meth)acrylates, hydroxyl group-containing (meth)acrylates, amino group-containing (meth)acrylates, epoxy group-containing (meth)acrylates, urethane bond-containing (meth)acrylates, and urea bond-containing (meth)acrylates.

[0166] The structural unit derived from the (meth)acryloyl group-containing compound is preferably a structural unit derived from a compound containing two or more (meth)acryloyl groups in one molecule, from the viewpoint of easily improving the pressure resistance of the hollow particles and easily suppressing a decrease in pressure resistance at high temperatures.

[0167] In the case where the shell of the hollow particles of the present invention includes a structural unit from the above-mentioned free radical polymerizable compound, the content of the structural unit from the above-mentioned free radical polymerizable compound is not particularly limited, and is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less relative to 100% by mass of the resin. In addition, the content of the structural unit from the above-mentioned free radical polymerizable compound can be, for example, 1% by mass or more, or 5% by mass or more relative to 100% by mass of the resin. By including the structural unit from the above-mentioned free radical polymerizable compound, the crosslinking density of the shell is sometimes increased and the pressure resistance of the hollow particles is increased. On the other hand, when the content of the structural unit from the above-mentioned free radical polymerizable compound is below the above-mentioned upper limit value, it is easy to obtain a synergistic effect of a structure polymerized with at least one selected from a carbamate bond and a urea bond and a (meth) acryloyl group.

[0168] In the present invention, from the viewpoint of improving the pressure resistance of the hollow particles and suppressing the decrease in pressure resistance at high temperatures, the total content of the structural unit derived from the above-mentioned isocyanate group-containing compound, the structural unit derived from the above-mentioned active hydrogen compound, and the structural unit derived from the above-mentioned radical polymerizable compound is preferably 95% by mass or more, more preferably 97% by mass or more, further preferably 99% by mass or more, and most preferably 100% by mass, relative to 100% by mass of the resin.

[0169] From the viewpoint of efficiently allowing the reaction between the isocyanate group-containing compound and the active hydrogen compound to proceed, the content of the structural unit derived from the carboxyl group-containing compound such as (meth)acrylic acid is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, based on 100% by mass of the resin.

[0170] The content of the shell raw material in the mixed solution is not particularly limited, but is preferably 15 to 50% by mass, more preferably 20 to 40% by mass, relative to 100% by mass of the total mass of the components in the mixed solution excluding the aqueous medium.

[0171] (B) Hydrophobic solvent

[0172] The hydrophobic solvent used in the production method of the present invention is a non-polymerizable organic solvent that is poorly soluble in water.

[0173] The hydrophobic solvent acts as a spacer material for forming a hollow portion inside the particle. In the suspension step described later, a suspension in which droplets of the shell raw material composition containing the hydrophobic solvent are dispersed in an aqueous medium is obtained. In the suspension step, phase separation occurs in the droplets of the shell raw material composition, and as a result, the hydrophobic solvent with low polarity tends to concentrate inside the droplets. Finally, in the droplets of the shell raw material composition, the hydrophobic solvent is distributed inside according to their respective polarities, and other materials except the hydrophobic solvent are distributed around them.

[0174] Then, in the polymerization step described below, an aqueous dispersion containing precursor particles enclosing the hydrophobic solvent can be obtained. That is, the hydrophobic solvent is concentrated inside the particles, so that hollow parts filled with the hydrophobic solvent are formed inside the obtained precursor particles.

[0175] The hydrophobic solvent can be appropriately selected from known hydrophobic solvents without particular limitation, and examples thereof include esters such as ethyl acetate and butyl acetate, ether esters such as propylene glycol monomethyl ether acetate and propylene glycol monoethyl ether acetate, and hydrocarbon solvents. Hydrocarbon solvents are particularly preferred.

[0176] Examples of hydrocarbon solvents include aliphatic hydrocarbons including chain hydrocarbon solvents such as pentane, hexane, heptane, octane, 2-methylbutane and 2-methylpentane, paraffin solvents, and cyclic hydrocarbon solvents such as cyclohexane, methylcyclohexane and cycloheptane; and aromatic hydrocarbons such as benzene, toluene and xylene.

[0177] As the hydrocarbon solvent, a hydrocarbon solvent having 4 to 7 carbon atoms is preferred, and a hydrocarbon solvent having 5 to 7 carbon atoms is more preferred. Here, the hydrocarbon solvent may be an aromatic hydrocarbon or an aliphatic hydrocarbon, and an aliphatic hydrocarbon is particularly preferred, a cyclic hydrocarbon solvent is more preferred, and at least one selected from cyclohexane, cycloheptane, and methylcyclohexane is further preferred.

[0178] In addition, the hydrophobic solvents can be used alone or in combination of two or more.

[0179] In addition, although not particularly limited, from the viewpoint of easy removal in the solvent removal step described later, the boiling point of the hydrophobic solvent is preferably 130°C or lower, more preferably 100°C or lower. On the other hand, from the viewpoint of easy inclusion in the precursor particles, it is preferably 50°C or higher, more preferably 60°C or higher.

[0180] In addition, when the hydrophobic solvent is a mixed solvent containing multiple hydrophobic solvents and has multiple boiling points, the boiling point of the solvent with the highest boiling point among the solvents contained in the mixed solvent is preferably below the above-mentioned upper limit value, and the boiling point of the solvent with the lowest boiling point among the solvents contained in the mixed solvent is preferably above the above-mentioned lower limit value.

[0181] In addition, the hydrophobic solvent preferably has a relative dielectric constant of 2.5 or less at 20° C. The relative dielectric constant is one of the indicators indicating the polarity of a compound. It is believed that when the relative dielectric constant of the hydrophobic solvent is sufficiently small to be 2.5 or less, phase separation in the droplets of the shell raw material composition proceeds rapidly and a hollow portion is easily formed.

[0182] Examples of hydrophobic solvents having a relative dielectric constant of 2.5 or less at 20° C. are as follows. The values ​​in parentheses are relative dielectric constants.

[0183] Cyclohexane (2.0), toluene (2.4), hexane (1.9).

[0184] Regarding the relative dielectric constant at 20°C, the values ​​and other technical information described in known documents (e.g., "Basic Handbook of Chemistry" compiled by the Chemical Society of Japan, revised 4th edition, Maruzen Co., Ltd., published on September 30, 1996, pages II-498 to II-503) can be referred to. As a method for measuring the relative dielectric constant at 20°C, for example, a relative dielectric constant test performed in accordance with 23 of JIS C 2101:1999 and with the measuring temperature at 20°C can be cited.

[0185] The porosity of the hollow particles can be adjusted by changing the amount of the hydrophobic solvent in the mixed solution. In the suspension step described later, the polymerization reaction is carried out in a state where the oil droplets containing the shell raw material and the like contain the hydrophobic solvent, so there is a tendency that the porosity of the obtained hollow particles is higher as the content of the hydrophobic solvent increases.

[0186] In the present invention, from the viewpoint of easily controlling the particle size of the hollow particles, easily improving the porosity while maintaining the strength of the hollow particles, and easily reducing the amount of residual hydrophobic solvent in the particles, the content of the hydrophobic solvent in the mixed solution is preferably 50 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the shell raw material. The content of the hydrophobic solvent in the mixed solution is more preferably 70 parts by mass or more and 300 parts by mass or less relative to 100 parts by mass of the shell raw material, and further preferably 80 parts by mass or more and 200 parts by mass or less.

[0187] (C) Polymerization initiator

[0188] When the shell raw material contains a (meth)acryloyl group-containing compound, the mixed liquid preferably contains a polymerization initiator for causing a radical polymerization reaction of the (meth)acryloyl group.

[0189] As a polymerization initiator, an oil-soluble polymerization initiator is preferably used. When an oil-soluble polymerization initiator is used, in the suspension process described later, the droplets of the shell raw material composition contain an oil-soluble polymerization initiator, a shell raw material, and a hydrophobic solvent. The droplets of the shell raw material composition are tiny oil droplets, and the oil-soluble polymerization initiator generates polymerization initiation free radicals inside the tiny oil droplets. Therefore, it is possible to manufacture precursor particles of a target particle size without excessive growth of the tiny oil droplets. In the suspension polymerization method using such an oil-soluble polymerization initiator, there is no chance that the polymerization initiator contacts the (meth)acryloyl compound in the aqueous medium. Therefore, by using an oil-soluble polymerization initiator, it is possible to suppress the generation of excess resin particles such as dense particles with a smaller particle size, in addition to the target resin particles with a hollow portion, as by-products.

[0190] The oil-soluble polymerization initiator is not particularly limited as long as it is a lipophilic polymerization initiator having a solubility of 0.2% by mass or less in water at 15° C., and examples thereof include organic peroxides such as benzoyl peroxide, lauroyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxydiethylacetate, and tert-butyl peroxypivalate; azo compounds such as 2,2'-azobis(2,4-dimethylvaleronitrile), azobisisobutyronitrile, and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), etc. Among them, it is preferred to use an organic peroxide as the oil-soluble polymerization initiator from the viewpoint that the cross-linking density of the shell is increased, the pressure resistance is easily improved, and the reduction of the pressure resistance at high temperature is easily suppressed.

[0191] The content of the polymerization initiator relative to 100 parts by mass of the (meth)acryloyl group-containing compound in the mixed solution is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and further preferably 2 parts by mass or more as the lower limit, and is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and further preferably 6 parts by mass or less as the upper limit.

[0192] When the content of the polymerization initiator is not less than the above lower limit, the polymerization reaction can be sufficiently carried out, and when the content of the polymerization initiator is not more than the above upper limit, the possibility of the polymerization initiator remaining after the polymerization reaction is completed is small, and the possibility of unexpected side reactions occurring is also small.

[0193] (D) Dispersion stabilizer

[0194] The dispersion stabilizer is an agent for dispersing the droplets of the shell raw material composition in the aqueous medium in the suspension step. Examples of the dispersion stabilizer include inorganic dispersion stabilizers, organic or inorganic water-soluble polymer stabilizers, and surfactants.

[0195] In the present invention, it is preferred to use an inorganic dispersion stabilizer as the dispersion stabilizer from the viewpoints of easily controlling the particle size of the droplets in the suspension, easily removing the dispersion stabilizer by a washing process, and suppressing the shell from becoming too thin and suppressing the decrease in the strength of the hollow particles. In addition, when a water-soluble polymer stabilizer or a surfactant is used as the dispersion stabilizer, sometimes a part of the dispersion stabilizer reacts with the isocyanate group-containing compound to reduce the crosslinking density of the shell, but by using an inorganic dispersion stabilizer as the dispersion stabilizer, the decrease in the crosslinking density of the shell can be suppressed.

[0196] Examples of the inorganic dispersion stabilizer include sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate; metal oxides such as aluminum oxide and titanium oxide; metal hydroxides such as aluminum hydroxide, magnesium hydroxide, calcium hydroxide, barium hydroxide, and iron hydroxide; and inorganic compounds such as silicon dioxide. These inorganic dispersion stabilizers can be used alone or in combination of two or more.

[0197] When an epoxy group-containing compound is used as the active hydrogen compound, the suspension described below is preferably acidic or alkaline from the viewpoint of ring-opening the epoxy group. To make the suspension alkaline, a basic salt such as the above-mentioned metal hydroxide is preferably used as a dispersion stabilizer.

[0198] As the inorganic dispersion stabilizer, an inorganic dispersion stabilizer that is poorly soluble in water can be preferably used. Here, poorly soluble in water means that the solubility in water at 25° C. is preferably less than 1 g / L.

[0199] As the poorly water-soluble inorganic dispersion stabilizer, metal hydroxides are preferred, and magnesium hydroxide is more preferred.

[0200] In the present invention, it is particularly preferred to use the sparingly water-soluble inorganic dispersion stabilizer in a state dispersed in an aqueous medium in the form of colloidal particles, i.e., in a colloidal dispersion liquid containing sparingly water-soluble inorganic dispersion stabilizer colloid particles. Thus, the inorganic dispersion stabilizer can be easily removed by the washing step described later.

[0201] The colloidal dispersion containing the sparingly water-soluble inorganic dispersion stabilizer colloidal particles can be prepared, for example, by reacting at least one selected from alkali metal hydroxides and alkaline earth metal hydroxides with a water-soluble polyvalent metal salt (excluding alkaline earth metal hydroxides) in an aqueous medium.

[0202] Examples of the alkali metal hydroxide salt include lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. Examples of the alkaline earth metal hydroxide salt include barium hydroxide, calcium hydroxide, etc.

[0203] As the water-soluble polyvalent metal salt, any polyvalent metal salt showing water solubility other than the compounds belonging to the above-mentioned alkaline earth metal hydroxide salts may be mentioned, for example: magnesium metal salts such as magnesium chloride, magnesium phosphate, and magnesium sulfate; calcium metal salts such as calcium chloride, calcium nitrate, calcium acetate, and calcium sulfate; aluminum metal salts such as aluminum chloride and aluminum sulfate; barium salts such as barium chloride, barium nitrate, and barium acetate; zinc salts such as zinc chloride, zinc nitrate, and zinc acetate, etc. Among these, magnesium metal salts, calcium metal salts, and aluminum metal salts are preferred, magnesium metal salts are more preferred, and magnesium chloride is particularly preferred.

[0204] There is no particular limitation on the method for reacting at least one selected from the above-mentioned alkali metal hydroxides and alkaline earth metal hydroxides with the above-mentioned water-soluble polyvalent metal salt in an aqueous medium. For example, an aqueous solution of at least one selected from the above-mentioned alkali metal hydroxides and alkaline earth metal hydroxides can be mixed with an aqueous solution of a water-soluble polyvalent metal salt.

[0205] Furthermore, colloidal silica can also be used as a colloidal dispersion containing colloid particles of an inorganic dispersion stabilizer that is sparingly soluble in water.

[0206] Examples of organic water-soluble polymer stabilizers include polyvinyl alcohol, polycarboxylates (polyacrylic acid, etc.), celluloses (hydroxyethyl cellulose, carboxymethyl cellulose, methyl cellulose, ethyl cellulose, etc.), polyvinyl pyrrolidone, polyacrylimide, polyethylene oxide, and poly(hydroxystearic acid-g-methyl methacrylate-co-methacrylic acid) copolymers.

[0207] Examples of the inorganic water-soluble polymer stabilizer include sodium tripolyphosphate and the like.

[0208] The surfactant refers to a compound having both a hydrophilic group and a hydrophobic group in one molecule, and examples thereof include ionic surfactants such as known anionic surfactants, cationic surfactants, and amphoteric surfactants, and nonionic surfactants.

[0209] In addition, the solubility of the water-soluble polymer stabilizer and the surfactant in water at 25° C. is usually 1 g / L or more.

[0210] The content of the dispersion stabilizer is not particularly limited, and is preferably 0.5 to 15 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total mass of the shell raw material and the hydrophobic solvent. When the content of the dispersion stabilizer is above the lower limit, the droplets of the shell raw material composition can be fully dispersed in the suspension without being combined. On the other hand, when the content of the dispersion stabilizer is below the upper limit, the viscosity of the suspension can be prevented from increasing during granulation, and the undesirable situation of clogging of the suspension in the granulator can be avoided.

[0211] The content of the dispersion stabilizer is preferably 0.5 to 15 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the aqueous medium.

[0212] (E) Water-based media

[0213] In the present invention, the aqueous medium refers to a medium selected from water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent.

[0214] When a mixture of water and a hydrophilic solvent is used, it is important that the polarity of the mixture as a whole does not become too low from the viewpoint of forming droplets of the shell raw material composition. In this case, the mass ratio of water to the hydrophilic solvent (water:hydrophilic solvent) can be, for example, 99:1 to 50:50.

[0215] The hydrophilic solvent in the present invention is not particularly limited as long as it is a solvent that is fully miscible with water without phase separation. Examples of the hydrophilic solvent include alcohols such as methanol and ethanol; tetrahydrofuran (THF); and dimethyl sulfoxide (DMSO).

[0216] The content of the aqueous medium is not particularly limited. From the viewpoint of making the particle size and porosity of the hollow particles within the preferred range described below, the lower limit is preferably 200 parts by mass or more, more preferably 400 parts by mass or more, and further preferably 600 parts by mass or more, relative to 100 parts by mass of the shell raw material contained in the mixed solution. The upper limit is preferably 1000 parts by mass or less, and more preferably 800 parts by mass or less.

[0217] The mixed solution may further contain other materials different from the above-mentioned materials (A) to (E) within a range not impairing the effects of the present invention.

[0218] A mixed solution can be obtained by mixing the above-mentioned materials and other materials as required and stirring them appropriately. In the mixed solution, the oil phase containing the above-mentioned (A) shell raw material, (B) hydrophobic solvent and (C) lipophilic materials such as polymerization initiator is dispersed in a water phase containing (D) dispersion stabilizer and (E) aqueous medium in a particle size of about several mm. The dispersion state of these materials in the mixed solution can also be observed by naked eyes depending on the type of materials.

[0219] In the mixed solution preparation step, the mixed solution can be obtained by simply mixing the above-mentioned materials with other materials as needed and stirring appropriately, but from the viewpoint that the shell is easy to become uniform, it is preferred to separately prepare an oil phase containing a shell raw material, a hydrophobic solvent and a polymerization initiator and an aqueous phase containing a dispersion stabilizer and an aqueous medium in advance, and then mix them to prepare a mixed solution. In the present invention, a colloidal dispersion in which a poorly water-soluble inorganic dispersion stabilizer is dispersed in an aqueous medium in the form of colloidal particles can be preferably used as the aqueous phase.

[0220] By separately preparing the oil phase and the water phase in advance and then mixing them, hollow particles having a uniform composition of the shell portion can be produced, and the particle size of the hollow particles can also be easily controlled.

[0221] (2) Suspension process

[0222] The suspending step is a step of suspending the mixed solution to prepare a suspension in which droplets of the shell raw material composition containing a hydrophobic solvent are dispersed in an aqueous medium.

[0223] The suspension method for forming the droplets of the shell raw material composition is not particularly limited, and a known suspension method can be used. As the disperser used when preparing the suspension, for example, a horizontal or vertical pipeline disperser such as Milder manufactured by Pacific Machinery Co., Ltd., Cavitron manufactured by Eurotec Co., Ltd., and a pipeline disperser manufactured by IKA (e.g., DISPAX-REACTOR (registered trademark) DRS) can be used; an emulsifying disperser such as the Homomixer MARK II series manufactured by Plemix Co., Ltd. can be used.

[0224] In the suspension prepared in the suspension step, droplets of the shell raw material composition containing the lipophilic material and having a particle size of about 1 to 50 μm are uniformly dispersed in the aqueous medium. Such droplets of the shell raw material composition are not easily observed with the naked eye, but can be observed using a known observation device such as an optical microscope.

[0225] In the suspension step, phase separation occurs in the droplets of the shell raw material composition, so the low-polarity hydrophobic solvent tends to concentrate inside the droplets. As a result, the obtained droplets have the hydrophobic solvent distributed inside and materials other than the hydrophobic solvent distributed around them.

[0226] The droplets of the shell raw material composition dispersed in the aqueous medium are formed by surrounding the oil-soluble shell raw material composition with the dispersion stabilizer. The droplets of the shell raw material composition contain an oil-soluble polymerization initiator, a shell raw material, and a hydrophobic solvent.

[0227] (3) Polymerization process

[0228] This step is a step of polymerizing the shell raw material contained in the suspension obtained in the above-mentioned suspension step to form precursor particles having a shell containing a resin and a hollow part surrounded by the shell and filled with a hydrophobic solvent. Through this step, a precursor composition in which the precursor particles are dispersed in an aqueous medium is obtained.

[0229] The polymerization method is not particularly limited, and for example, a known polymerization method such as a batch method (intermittent method), a semi-continuous method, and a continuous method can be adopted.

[0230] The polymerization temperature is appropriately adjusted so as to allow the reaction of the compounds contained in the shell raw material to proceed, and is not particularly limited. When at least one or both of the reaction of the isocyanate group-containing compound with the active hydrogen compound and the polymerization reaction of the (meth)acryloyl group are carried out, the polymerization temperature is preferably 40 to 95°C, more preferably 50 to 90°C.

[0231] The polymerization reaction time is preferably 1 to 48 hours, and preferably 5 hours or more from the viewpoint of reducing the amount of unreacted shell raw material remaining. From the viewpoint of ease of production, the upper limit of the polymerization reaction time is preferably 36 hours or less.

[0232] (4) Solvent Removal Process

[0233] This step is a step of removing the hydrophobic solvent contained in the precursor particles. In the present invention, a method of removing the hydrophobic solvent contained in the precursor particles in a gas after solid-liquid separation of a slurry formed by dispersing the precursor particles in an aqueous medium can be adopted, and a method of removing the hydrophobic solvent contained in the precursor particles in the slurry can also be adopted.

[0234] The method for the solid-liquid separation is not particularly limited, and examples thereof include centrifugal separation, filtration, static separation, etc. Filtration is particularly preferred from the viewpoint of easy operation and high removal efficiency of the dispersion stabilizer.

[0235] The precursor particles after solid-liquid separation may be pre-dried before removing the hydrophobic solvent. The pre-drying may be performed, for example, by drying the solid content including the precursor particles obtained by solid-liquid separation using a drying device such as a dryer or a drying tool such as a hand dryer.

[0236] Strictly speaking, "in gas" in this process refers to an environment where there is no liquid component at all outside the precursor particles and an environment where there is only a very small amount of liquid component outside the precursor particles that does not affect the degree of removing the hydrophobic solvent. "In gas" can be changed to a state where the precursor particles are not present in the slurry, and can also be changed to a state where the precursor particles are present in the dry powder. That is, it is important to remove the hydrophobic solvent under an environment where the precursor particles are in direct contact with the external gas.

[0237] The method for removing the hydrophobic solvent in the precursor particles in the gas is not particularly limited, and a known method can be adopted. Examples of the method include reduced pressure drying, heating drying, air flow drying, and a combination of these methods.

[0238] In particular, when the heating drying method is used, the heating temperature needs to be above the boiling point of the hydrophobic solvent and below the highest temperature at which the shell structure of the precursor particles does not collapse. Therefore, depending on the composition of the shell in the precursor particles and the type of the hydrophobic solvent, the heating temperature can be, for example, 50 to 200°C, 70 to 200°C, or 100 to 200°C.

[0239] By the drying operation in the gas, the hydrophobic solvent inside the precursor particles is replaced by the external gas, and as a result, hollow particles having the hollow part occupied by the gas are obtained.

[0240] The dry atmosphere is not particularly limited and can be appropriately selected according to the purpose of the hollow particles. As the dry atmosphere, for example, air, oxygen, nitrogen, argon, etc. can be considered. In addition, after the hollow particles are temporarily filled with gas, reduced pressure drying is carried out, thereby, hollow particles with a temporary vacuum inside can also be obtained.

[0241] As a method for removing the hydrophobic solvent contained in the precursor particles in the slurry formed by dispersing the precursor particles in the aqueous medium, for example, a method for evaporating and removing the hydrophobic solvent contained in the precursor particles in the slurry under a specified pressure can be cited, and more specifically, a method for evaporating and removing the hydrophobic solvent in the hollow particles by introducing an inert gas such as nitrogen, argon, helium, air or water vapor into the slurry under a specified pressure selected from high pressure, normal pressure and reduced pressure, etc. From the viewpoint of excellent removal efficiency of the hydrophobic solvent, it is particularly preferred to evaporate and remove the hydrophobic solvent in the hollow particles by introducing an inert gas into the slurry dispersed with the precursor particles under a specified pressure.

[0242] As a method for introducing the inert gas into the slurry, for example, a method of blowing the inert gas into the slurry can be preferably used.

[0243] In addition, from the viewpoint of reducing the residual amount of the hydrophobic solvent, the temperature when the inert gas is introduced into the slurry is preferably a temperature above the temperature after subtracting 35°C from the boiling point of the hydrophobic solvent, more preferably a temperature above the temperature after subtracting 30°C from the boiling point of the hydrophobic solvent, and further preferably a temperature above the temperature after subtracting 20°C from the boiling point of the hydrophobic solvent. Here, in the case where the above-mentioned hydrophobic solvent is a mixed solvent containing multiple hydrophobic solvents and has multiple boiling points, the boiling point of the hydrophobic solvent in the solvent removal process refers to the boiling point of the solvent with the highest boiling point in the solvent contained in the mixed solvent, that is, the highest boiling point among the multiple boiling points. In addition, the temperature when the inert gas is introduced into the slurry is usually set to a temperature above the polymerization temperature in the above-mentioned polymerization process. The temperature when the inert gas is introduced into the slurry is not particularly limited and can be 50 to 100°C.

[0244] The conditions for blowing the inert gas into the slurry are appropriately adjusted according to the type and amount of the hydrophobic solvent so as to remove the hydrophobic solvent contained in the precursor particles. For example, the inert gas may be blown at 1 to 3 L / min for 1 to 72 hours.

[0245] By introducing an inert gas into the slurry, a slurry of hollow particles containing the inert gas can be obtained. The slurry is separated into solid and liquid, and the remaining water in the obtained hollow particles is removed by drying, thereby obtaining hollow particles in which the hollow part is occupied by gas.

[0246] (5) Cleaning process

[0247] The method for producing hollow particles of the present invention preferably includes a washing step before the above-mentioned solvent removal step.

[0248] The washing step may be a step of removing the dispersion stabilizer from the precursor particles obtained in the above-mentioned polymerization step.

[0249] The cleaning process can be carried out by, for example, adding an acid or a base to the precursor composition obtained by the polymerization process, dissolving the dispersion stabilizer contained in the precursor particles in the aqueous medium, and then separating the precursor particles from the aqueous medium. When the dispersion stabilizer used is an inorganic dispersion stabilizer soluble in acid, it is preferred to add an acid, and when the dispersion stabilizer used is an inorganic dispersion stabilizer soluble in alkali, it is preferred to add an alkali.

[0250] When the dispersion stabilizer used is an inorganic dispersion stabilizer soluble in acid, an acid is added to the precursor composition to adjust the pH to preferably 6.5 or less, more preferably to 6 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as formic acid and acetic acid can be used, and sulfuric acid is particularly preferred from the viewpoint of high removal efficiency of the dispersion stabilizer and small burden on production equipment.

[0251] In the washing step, it is preferred to repeat the operation of washing and dehydrating the precursor particles separated after adding the acid or alkali several times. In addition, in the washing step, a small amount of nonionic surfactant may be added to the slurry to suppress the aggregation of the precursor particles.

[0252] The method for separating the precursor particles from the aqueous medium is not particularly limited, and for example, the same method as the above-mentioned solid-liquid separation method can be cited. From the viewpoint of easy operation and high removal efficiency of the dispersion stabilizer, filtration is particularly preferred. In addition, when separating the precursor particles from the aqueous medium, the precursor particles obtained by filtration etc. are preferably dehydrated by a known method.

[0253] (6) Others

[0254] As a process other than the above (1) to (5), for example, a replacement process inside the particle may be added. The replacement process inside the particle refers to a process of replacing the gas or liquid inside the hollow particle with another gas or liquid. By such replacement, the environment inside the hollow particle can be changed, or molecules can be selectively enclosed inside the hollow particle, or the chemical structure inside the hollow particle can be modified according to the application.

[0255] 2. Hollow particles

[0256] The hollow particles of the present invention are particles having a shell (outer shell) containing a resin and a hollow portion surrounded by the shell.

[0257] In the present invention, the hollow part is a hollow space that is clearly distinguished from the shell. The shell of the hollow particle may also have a porous structure, but in this case, the hollow part has a size that can be clearly distinguished from a large number of microscopic spaces uniformly dispersed in the porous structure. From the viewpoint of pressure resistance, etc., the hollow particle of the present invention preferably has a dense shell.

[0258] The hollow part of the hollow particles can be confirmed by, for example, SEM observation of a particle cross section or by directly observing the particles by TEM.

[0259] Furthermore, from the viewpoints of weight reduction, heat insulation, and the like, the hollow particles of the present invention preferably have a hollow portion filled with a gas such as air.

[0260] The shell of the hollow particles of the present invention may be a shell containing the following resin, wherein the resin contains a structure formed by polymerization of at least one selected from a carbamate bond and a urea bond and a (meth)acryloyl group. From the viewpoint of easily improving the pressure resistance of the hollow particles and easily suppressing the reduction of the pressure resistance at high temperatures, the shell of the hollow particles of the present invention preferably has a single-layer structure.

[0261] The resin contained in the shell may be, for example, a polyurethane urea-acrylic hybrid polymer, or a mixture of a polymer containing at least one selected from polyurethane and polyurea and a (meth)acrylic polymer. In addition, a polyurethane urea-acrylic hybrid polymer refers to a polymer containing a structure formed by polymerizing at least one selected from a carbamate bond and a urea bond and a (meth)acryloyl group. Among them, a polymer containing a structure formed by polymerizing a carbamate bond and a (meth)acryloyl group without a urea bond is sometimes referred to as a polyurethane-acrylic hybrid polymer, and a polymer containing a structure formed by polymerizing a urea bond and a (meth)acryloyl group without a carbamate bond is sometimes referred to as a urea-acrylic hybrid polymer.

[0262] From the viewpoint of easily improving the pressure resistance of hollow particles and easily suppressing the decrease in pressure resistance at high temperatures, the hollow particles of the present invention preferably contain a polyurethane urea-acrylic hybrid polymer. As the polyurethane urea-acrylic hybrid polymer, for example, a polymer obtained by polymerizing a mixture of the compounds of (i) above, and a polymer obtained by polymerizing the compounds of (ii) above, etc. can be cited. Among them, from the viewpoint of easily improving the pressure resistance of hollow particles and easily suppressing the decrease in pressure resistance at high temperatures, a polyurethane urea-acrylic hybrid polymer obtained by polymerizing a mixture of the compounds of (i) above is preferred.

[0263] In addition, the polyurethane urea-acrylic hybrid polymer can be, for example, a polymer having a main chain formed by the polymerization of (meth)acryloyl groups and a cross-linked structure formed by at least one selected from a carbamate bond and a urea bond, or a polymer having a cross-linked structure formed by the polymerization of (meth)acryloyl groups in a polyurethane or polyurea generated by the reaction of a polyisocyanate with a polyamine or a polyol.

[0264] In the hollow particles of the present invention, the resin contained in the shell is a reaction product of the above-mentioned shell raw material. In the shell of the hollow particles of the present invention, from the viewpoint of suppressing the reduction of pressure resistance, the content of the resin in 100% by mass of the shell is preferably 96% by mass or more, more preferably 97% by mass or more, and further preferably 98% by mass or more.

[0265] The shell of the hollow particles of the present invention may be composed of the above-mentioned resin, but may further contain an additive different from the above-mentioned resin within a range not impairing the effects of the present invention.

[0266] The hollow particles of the present invention preferably have an infrared absorption spectrum of 1500 to 1550 cm-1 in the infrared absorption spectrum of the hollow particles measured by ATR-FTIR. -1 The maximum peak absorbance A1 in the range of 1700-1750cm -1The ratio of the absorbance A2 of the maximum peak in the range (A1 / A2) is 0.1 or more and 0.5 or less, and the ATR-FTIR is an FTIR (Fourier transform infrared spectrophotometer) using a total reflection measurement method. As a result, the content ratio of the structure formed by polymerization of at least one selected from a urethane bond and a urea bond and a (meth)acryloyl group is well balanced, so the pressure resistance of the hollow particles is easily improved, and the reduction of the pressure resistance at high temperature is easily suppressed.

[0267] The absorbance A1 is an absorbance corresponding to the absorption spectrum derived from the bending vibration of the NH group contained in the urethane bond, allophanate bond, oxazolidinone ring or urea bond, and is a wavelength appearing at 1500 to 1550 cm -1 It is calculated by the peak top intensity of the maximum peak within the range.

[0268] The absorbance A2 is an absorbance corresponding to the absorption spectrum derived from the stretching vibration of the carbonyl group contained in the structure obtained by polymerization of the (meth)acryloyl group, and is an absorbance appearing at 1700 to 1750 cm -1 It is calculated by the peak top intensity of the maximum peak within the range.

[0269] The carbamate bond formed by the reaction of isocyanate group and hydroxyl group sometimes reacts with hydroxyl group to form allophanate bond, for example, by making the content of active hydrogen compound be the above-mentioned preferred range, or by making the conditions of polymerization reaction be the above-mentioned preferred conditions, so that at least a portion of the carbamate bond remains. In addition, in the case of making isocyanate group-containing compound react with epoxy group-containing compound, there is the situation that isocyanate group and epoxy group form carbamate bond and form oxazolidone ring, but in the manufacture method of hollow particles of the present invention, owing to react at a temperature that is not easy to form oxazolidone ring, it is usually easy to form carbamate bond. Therefore, even in the case of the shell of the hollow particles of the present invention comprising allophanate bond or oxazolidone ring, if the above-mentioned ratio (A1 / A2) is within the above-mentioned range, the balance of the structure containing ratio of at least one selected from carbamate bond and urea bond and polymerized with (meth) acryloyl group is good. The lower limit of the ratio (A1 / A2) is more preferably 0.15 or more, and further preferably 0.20 or more. The upper limit of the ratio (A1 / A2) is more preferably 0.45 or less, and further preferably 0.40 or less.

[0270] The hollow particles of the present invention may have unreacted amino groups or hydroxyl groups on the particle surfaces, thereby sometimes improving the adhesion between the hollow particles of the present invention and the matrix resin in a mixture of the hollow particles of the present invention and the matrix resin.

[0271] The average circularity of the hollow particles of the present invention is 0.90 or more. From the viewpoint of improving the pressure resistance of the hollow particles and suppressing the decrease in pressure resistance at high temperatures, the average circularity of the hollow particles of the present invention is preferably 0.93 or more, more preferably 0.95 or more, and from the viewpoint of improving the dispersibility of the hollow particles, it is preferably 0.98 or less.

[0272] The circularity is defined as the value obtained by dividing the diameter of a circle having the same area as the projection image of the particle (equivalent circular area diameter) by the diameter of a circle having the same circumference as the projection image of the particle (equivalent circular circumference diameter). In the case where the particle is a perfect sphere, the circularity is 1, and the more complex the surface shape of the particle, the smaller the circularity value.

[0273] In the present invention, the circularity is measured using a flow particle imaging measurement device at an image resolution of 0.185 μm / pixel.

[0274] As a flow particle imaging measuring apparatus, for example, the product name "IF-3200" manufactured by JASCO International Co., Ltd. can be preferably used. The measuring sample is prepared by dispersing 0.10 to 0.12 g of hollow particles in an aqueous solution of sodium linear alkylbenzene sulfonate (concentration 0.3%) for 5 minutes using an ultrasonic cleaner.

[0275] The average circularity is the average value of the circularities of 1,000 to 3,000 particles selected at random.

[0276] In addition, the hollow particles of the present invention may contain a small amount of hollow particles with low roundness due to particle breakage, deformation, etc., or particles without a hollow portion as impurities. In 100 mass% of the hollow particles of the present invention, the proportion of particles with a roundness of less than 0.85 is preferably less than 5 mass%, more preferably less than 4 mass%, and further preferably less than 3 mass%.

[0277] Particles with a circularity of 0.85 or less are typically particles that are deformed or fractured, such as by depression. Compared with spherical hollow particles, such particles with low circularity have low porosity, and thus, have poor effects such as light weight and heat insulation. In the manufacturing process of the hollow particles of the present invention, the polymerization reaction in the shell is fully carried out, and thus, hollow particles with a small proportion of particles with low circularity can be obtained.

[0278] In addition, compared with spherical particles, particles with low circularity are easily condensed when dispersed in the matrix resin and have a problem of poor dispersibility. Furthermore, particles with low circularity are easily subjected to external pressure locally, so compared with spherical particles, there is also a problem of poor pressure resistance. When particles with low circularity are dispersed in the matrix resin, it is easy to generate agglomerates, which are easily subjected to external pressure, and thus have poor pressure resistance. Therefore, by reducing the proportion of particles with low circularity contained in the hollow particles, the dispersibility and pressure resistance of the hollow particles can be improved.

[0279] The hollow particles of the present invention, when the cumulative 50% particle size based on volume is set to D50 and the cumulative 90% particle size based on volume is set to D90, the ratio of D90 to D50 (D90 / D50) is 1.70 or less. The above ratio (D90 / D50) can be used as an indicator of the amount of coarse powder. The larger the above ratio (D90 / D50), the more coarse powder there is. When the above ratio (D90 / D50) is less than 1.70, the amount of coarse powder is sufficiently small, and the hollow particles are easily and evenly subjected to external forces, thereby having excellent pressure resistance. In addition, when the amount of coarse powder is sufficiently small, the polymerization reaction of the shell raw material is fully carried out in the shell, and from the viewpoint of the high crosslinking density of the shell, the pressure resistance of the hollow particles is also excellent. In addition, when the above ratio (D90 / D50) is below the above upper limit value, particles with small deviations in performance between particles can be obtained, for example, when manufacturing a sheet-like resin structure to which hollow particles are added, a product with uniform thickness can be manufactured. The ratio (D90 / D50) is preferably 1.50 or less, and more preferably 1.40 or less. The lower limit of the ratio (D90 / D50) is not particularly limited, and from the viewpoint of ease of production, it may be, for example, 1.20 or more, or 1.30 or more.

[0280] The D50 and D90 of the hollow particles can be determined from the volume-based particle size distribution of the hollow particles by measuring the particle size of the hollow particles using a particle size distribution analyzer using the Coulter counter method. The Coulter counter method is a method of measuring particle diameters using a resistance method known as the Coulter principle.

[0281] The lower limit of D50 of the hollow particles of the present invention is preferably 1.0 μm or more, more preferably 3.0 μm or more, and further preferably 5.0 μm or more. The upper limit of D50 of the hollow particles of the present invention is preferably 50.0 μm or less, more preferably 30.0 μm or less, and further preferably 20.0 μm or less.

[0282] When the D50 of the hollow particles is above the above lower limit, the dispersibility of the hollow particles becomes good. In addition, when the D50 of the hollow particles is within the above range, a uniform shell is easily formed, and the deviation of the shell thickness can be suppressed, thereby there is a tendency for the pressure resistance of the hollow particles to improve.

[0283] The micro compression fracture strength can be used as an indicator of the pressure resistance of micro materials. In the present invention, the micro compression fracture strength of hollow particles is the fracture strength when the hollow particles are compressed using a micro compression tester under the conditions of a maximum crushing test force of 2000mN and a load speed of 0.0466mN / s, and is measured in accordance with JIS R1639-5. The fracture strength is the strength at the moment when the particle breaks, that is, the moment when the compression displacement changes significantly, and is represented by the following formula (A).

[0284] Formula (A):

[0285] Cs=2.48P / πd 2

[0286] Cs: Breaking strength (MPa)

[0287] P: Test force at breaking point (N)

[0288] d: particle size (mm)

[0289] The micro-compression fracture strength of the hollow particles at 150°C can be used as an indicator of the pressure resistance of the hollow particles at high temperatures. The hollow particles of the present invention have a micro-compression fracture strength of 5.0 MPa or more at 150°C, have excellent elasticity and strength even at high temperatures, and have excellent pressure resistance. The micro-compression fracture strength of the hollow particles of the present invention at 150°C is preferably 7.5 MPa or more, more preferably 10.0 MPa or more, and further preferably 15.0 MPa or more. The hollow particles of the present invention having a micro-compression fracture strength of 15.0 MPa or more at 150°C have particularly excellent pressure resistance at high temperatures, so when added to a resin injection molded at 150°C to 300°C, the porosity maintenance rate after injection molding is significantly high.

[0290] For hollow particles having a micro-compression fracture strength of 15.0 MPa or more at 150°C, for example, it is effective to use a mixture of an isocyanate group-containing polyfunctional (meth)acrylate and at least one active hydrogen compound selected from polyamines, aliphatic polyols, and (meth)acrylic polymer polyols, or a mixture of a polyisocyanate and a hydroxyl group-containing (meth)acrylate as a shell raw material. Furthermore, it is also effective to adjust the content of the active hydrogen compound in the shell raw material so that the content of the structural unit derived from the active hydrogen compound contained in the shell is within the above-mentioned preferred range. It is inferred that by using such a shell raw material, the crosslinking density of the shell is easily increased, and therefore the micro-compression fracture strength at 150°C is improved.

[0291] In the hollow particles of the present invention, the upper limit of the micro-compression fracture strength at 150° C. is not particularly limited, and may be, for example, 30.0 MPa or less, or 25.0 MPa or less.

[0292] The micro-compression fracture strength of the hollow particles of the present invention at 23°C is not particularly limited, but is preferably 10.0 MPa or more, more preferably 12.5 MPa or more, and further preferably 15.0 MPa or more. In the hollow particles of the present invention, the upper limit of the micro-compression fracture strength at 23°C is not particularly limited, and may be, for example, 50.0 MPa or less, 40.0 MPa or less, or 30.0 MPa or less.

[0293] The ratio of the micro-compression fracture strength of the hollow particles of the present invention at 150°C to the micro-compression fracture strength at 23°C (micro-compression fracture strength at 150°C / micro-compression fracture strength at 23°C) is preferably 0.60 or more, more preferably 0.70 or more, and further preferably 0.80 or more. The closer this ratio is to 1, the more the decrease in the pressure resistance of the hollow particles at high temperatures is suppressed.

[0294] The hollow particles of the present invention preferably have a porosity of 60% or more. The higher the porosity of the hollow particles, the better the lightness and heat insulation properties. The upper limit of the porosity is not particularly limited, but from the viewpoint of suppressing the decrease in the pressure resistance of the hollow particles, it is preferably 85% or less, more preferably 80% or less, and further preferably 75% or less.

[0295] The porosity of hollow particles is calculated based on the apparent density D of the hollow particles. 1 and true density D 0 Figure it out.

[0296] The apparent density of hollow particles is D 1 The determination method is as follows. First, in a volume of 100 cm 3 Fill the volumetric flask to about 30 cm 3 The mass of the hollow particles filled was accurately weighed. Next, the volumetric flask filled with the hollow particles was accurately filled with isopropyl alcohol up to the mark, while being careful not to mix in bubbles. The mass of isopropyl alcohol added to the volumetric flask was accurately weighed, and the apparent density D of the hollow particles was calculated based on the following formula (I): 1 (g / cm 3 ).

[0297] Formula (I)

[0298] Apparent density D 1 = [mass of hollow particles] / (100 - [mass of isopropyl alcohol] / [specific gravity of isopropyl alcohol at the measurement temperature])

[0299] Apparent density D 1 This corresponds to the specific gravity of the entire hollow particle when the hollow portion is regarded as a part of the hollow particle.

[0300] True density of hollow particles D0 The method for measuring is as follows. The hollow particles are crushed in advance and then placed in a container with a capacity of 100 cm 3 A volumetric flask is filled with about 10 g of hollow particle fragments, and the mass of the filled fragments is accurately weighed. Then, isopropanol is added to the volumetric flask in the same manner as the above-mentioned apparent density measurement, and the mass of isopropanol is accurately weighed. The true density D of the hollow particles is calculated based on the following formula (II): 0 (g / cm 3 ).

[0301] Formula (II)

[0302] True density D 0 = [mass of hollow particle fragments] / (100 - [mass of isopropyl alcohol] / [specific gravity of isopropyl alcohol at the measurement temperature])

[0303] True density D 0 It is equivalent to the specific gravity of the shell part of the hollow particle. 0 When the hollow portion is considered as part of the hollow particle.

[0304] The porosity (%) of the hollow particles is determined by the apparent density D of the hollow particles. 1 and true density D 0 It is calculated by the following formula (III).

[0305] Formula (III)

[0306] Porosity (%) = 100 - (apparent density D 1 / True density D 0 )×100

[0307] The hollow particles of the present invention may have one or two or more hollow parts, but preferably have only one hollow part from the viewpoint of maintaining a good balance between high porosity and mechanical strength.

[0308] In the case where the hollow particles of the present invention have only one hollow part, a small amount of hollow particles having two or more hollow parts or particles having no hollow part may be contained in the hollow particles of the present invention as impurities. In the hollow particles of the present invention, the number ratio of particles having only one hollow part is preferably 90% or more, more preferably 95% or more.

[0309] Furthermore, the shell of the hollow particles of the present invention and, when the hollow particles have two or more hollow parts, the partition walls separating adjacent hollow parts may be porous, but are preferably dense from the viewpoint of improving pressure resistance and the like.

[0310] An example of the image of the shape of the hollow particles of the present invention is a bag formed of a thin film and inflated with gas, and its cross-sectional view is as follows: Figure 1 The hollow particle 10 in (4) is shown. In this example, a thin film is provided on the outside, and the inside is filled with gas.

[0311] In addition, the particle shape can be confirmed by, for example, SEM or TEM.

[0312] In the present invention, the thermal decomposition temperature of the hollow particles is preferably 300°C or higher, more preferably 350°C or higher. Hollow particles having a thermal decomposition temperature above the lower limit have excellent heat resistance. The upper limit of the thermal decomposition temperature of the hollow particles is not particularly limited, and may be, for example, 400°C or higher.

[0313] In the present invention, the thermal decomposition temperature is the temperature at which the weight is reduced by 5% when heated under nitrogen atmosphere at an air flow rate of 230 mL / min and a heating rate of 10° C. / min, and can be measured by a TG-DTA apparatus.

[0314] The amount of gas generated from the hollow particles of the present invention at 150° C. for 1 hour is preferably 500 ppm or less, more preferably 200 ppm or less, further preferably 100 ppm or less, and further preferably 50 ppm or less.

[0315] The gas generation amount is the ratio of the mass of gas generated from the hollow particles within 1 hour when the hollow particles are placed at 150° C. to the mass of the hollow particles before being placed at 150° C. The mass of the hollow particles before being placed at 150° C. is usually the mass of the hollow particles at room temperature.

[0316] When the above-mentioned gas generation amount is below the above-mentioned upper limit value, the reduction of the rigidity of the shell at high temperature can be suppressed, and the reduction of the pressure resistance at high temperature of the hollow particles can be suppressed. In addition, it can be considered that the less the gas generation amount at high temperature, the fewer the side reaction products contained in the hollow particles, and it can be considered that the fewer the side reaction products, the higher the crosslinking density of the shell.

[0317] Examples of uses of the hollow particles of the present invention include various components used in various fields such as automobiles, electrical, electronic, construction, aviation, and aerospace, food containers, footwear such as sports shoes and sandals, home appliance parts, bicycle parts, stationery, tools, filaments for 3D printers, lightweight agents, heat insulating agents, sound insulating agents, or refractive index adjusters in buoyancy materials such as composite foam, etc.

[0318] In addition, the hollow particles of the present invention satisfy the heat insulation and cushioning properties required of primer materials, and also satisfy the heat resistance suitable for thermal paper applications. In addition, the hollow particles of the present invention are also useful as plastic pigments having excellent gloss and hiding power.

[0319] Furthermore, the hollow particles of the present invention can contain useful components such as fragrances, chemicals, pesticides, and ink components by methods such as impregnation treatment, reduced pressure or pressurized impregnation treatment, and can therefore be used for various purposes depending on the components contained therein.

[0320] Furthermore, the hollow particles of the present invention are also preferably used as rust preventives. The hollow particles of the present invention are also useful as additives for reducing electrical conductivity, so for example, a coating containing the hollow particles of the present invention can be used as an anti-rust coating (coating base, lubricating coating, etc.) for improving the corrosion resistance and rust resistance of steel materials, etc. In addition, the hollow particles added to the anti-rust coating can also contain an anti-rust additive.

[0321] 3. Resin composition

[0322] The resin composition of the present invention contains at least the hollow particles of the present invention and a matrix resin, and is typically in a liquid state. The resin composition of the present invention can be generally used as a molding material for a resin structure described below.

[0323] The resin composition of the present invention contains the hollow particles of the present invention described above, and the hollow particles have excellent pressure resistance at high temperatures and can maintain pores even at high temperatures. Therefore, by using the resin composition of the present invention, the porosity is high, thereby obtaining a resin structure with excellent effects such as light weight and heat insulation.

[0324] As the liquid resin composition, for example, a liquid resin composition including a liquid matrix resin before the curing reaction, a liquid resin composition obtained by dissolving or dispersing each component in a solvent, etc. can be cited. Here, the liquid matrix resin before the curing reaction and the matrix resin dissolved or dispersed in the solvent can be a thermosetting resin or a thermoplastic resin. Alternatively, the resin composition can be made liquid by melting the matrix resin.

[0325] [Base resin]

[0326] Examples of the matrix resin include curable resins such as thermosetting resins, photocurable resins, and room temperature curable resins, and thermoplastic resins. In particular, thermosetting resins, room temperature curable resins, and thermoplastic resins can be preferably used.

[0327] In addition, the matrix resin contained in the resin composition can be an unreacted monomer, prepolymer or macromonomer, or a polymer, or a precursor of a curable resin such as polyamic acid. The matrix resin contained in the resin composition of the present invention is cured by, for example, heating, light, or using a curing agent, a polymerization initiator or a catalyst, so as to function as a binder.

[0328] As the thermosetting resin, known thermosetting resins can be used without particular limitation, and examples thereof include phenolic resins, melamine resins, urea resins, unsaturated polyester resins, epoxy resins, modified epoxy resins, polyurethane resins, silicone resins, alkyd resins, benzoxazine resins, allyl resins, aniline resins, modified polyphenylene ether resins, thermosetting polyimide resins, maleimide resins, bismaleimide triazine resins, liquid crystalline polyester resins, vinyl ester resins, cyanate ester resins, or precursors of these resins before curing.

[0329] Examples of the room temperature curable resin include adhesives that can be cured at room temperature by adding a catalyst, such as epoxy adhesives, silicone adhesives, and acrylic adhesives.

[0330] Examples of thermoplastic resins include polyolefin resins such as polypropylene and polyethylene, polyamide resins such as PA6, PA66, and PA12, polycarbonate resins, polyphenylene sulfide resins, polyetheretherketone resins, polystyrene resins, polyphenylene ether resins, liquid crystal polymers (LCP), polyetheretherketone resins, polyimide resins, polyamideimide resins, polyetherimide resins, polyvinyl chloride resins, poly(meth)acrylate resins, polyvinylidene fluoride resins, acrylonitrile-butadiene-styrene copolymer (ABS) resins, acrylonitrile-styrene copolymer (AS) resins, polyphenylene ether resins, polyester resins, polytetrafluoroethylene resins, thermoplastic elastomers, etc. In addition, thermoplastic elastomers are substances that usually exhibit rubber elasticity at room temperature (25° C.) and can be plasticized and molded at high temperatures. Examples of the thermoplastic elastomer include polyurethane elastomers, styrene elastomers, olefin elastomers, amide elastomers, and ester elastomers.

[0331] These base resins can be used alone or in combination of two or more.

[0332] About the resin composition of the present invention containing epoxy resin as matrix resin, it is preferred to make the matrix resin and the hollow particle of the present invention have excellent adhesion in the resin structure obtained by curing the resin composition. The hollow particle of the present invention usually has unreacted amino or hydroxyl on the particle surface. Therefore, when containing epoxy resin as matrix resin, it can be inferred that the epoxy group in the matrix resin is combined with the amino or hydroxyl reaction present on the surface of the hollow particle, so that the adhesion improves.

[0333] Examples of the epoxy resin used as the matrix resin include biphenylol epoxy resins, bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol AF epoxy resins, dicyclopentadiene epoxy resins, trisphenol epoxy resins, naphthol novolac epoxy resins, phenol novolac epoxy resins, tert-butyl-catechol epoxy resins, naphthalene epoxy resins, naphthol epoxy resins, anthracene epoxy resins, glycidylamine epoxy resins, glycidyl ester epoxy resins, cresol novolac epoxy resins, and bisphenol A epoxy resins. Lacquer type epoxy resin, phenol aralkyl type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexanedimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, isocyanurate type epoxy resin, phenol phthalamidine type epoxy resin, phenolphthalein type epoxy resin, etc. These epoxy resins can be used alone or in combination of two or more.

[0334] In the resin composition of the present invention, the content of the matrix resin is not particularly limited, and is usually 40 to 95% by mass, preferably 50 to 95% by mass, more preferably 70 to 95% by mass, and can be 85 to 95% by mass in the total solid content of 100% by mass of the resin composition. When the content of the matrix resin is above the above lower limit, the moldability of the resin composition is excellent, and the mechanical strength when the resin structure is made can be improved. When the content of the matrix resin is below the above upper limit, hollow particles can be fully contained, and therefore, the resin composition brought by the hollow particles has excellent effects such as light weight and heat insulation.

[0335] In the present invention, the solid content refers to all components except the solvent, and liquid monomers and the like are included in the solid content.

[0336] [Hollow particles]

[0337] The hollow particles contained in the resin composition of the present invention are the hollow particles of the present invention described above.

[0338] In the resin composition of the present invention, the content of hollow particles is not particularly limited, in the total solid content 100% by mass of the resin composition, as a lower limit, preferably more than 5% by mass, more preferably more than 10% by mass, as an upper limit, preferably less than 70% by mass, more preferably less than 50% by mass, further less than 30% by mass. When the content of hollow particles is more than the above-mentioned lower limit, the lightweight, heat-insulating effects of the resin composition brought by the hollow particles are excellent. When the content of hollow particles is below the above-mentioned upper limit, it is possible to make the resin composition fully contain matrix resin, therefore, it is possible to suppress the reduction of physical properties when making a resin structure, so that mechanical strength is improved.

[0339] [Solvent]

[0340] The resin composition of the present invention may further contain a solvent for dissolving or dispersing each component. As the solvent, a known solvent can be used, and the solvent can be appropriately selected according to the type of the matrix resin.

[0341] [Other additives]

[0342] The resin composition of the present invention may further contain additives such as a curing agent, a curing accelerator, a polymerization initiator, a UV absorber, a colorant, a heat stabilizer, and a filler as necessary within a range not impairing the effects of the present invention.

[0343] 4. Resin structure

[0344] The resin structure of the present invention comprises the hollow particles of the present invention and a matrix resin. Since the resin structure of the present invention contains the hollow particles, it is endowed with properties such as light weight and heat insulation.

[0345] The resin structure of the present invention may be a structure obtained by solidifying the resin composition of the present invention described above into a desired shape, or may be a structure obtained by melt-kneading the hollow particles of the present invention and a thermoplastic resin and molding the resultant mixture.

[0346] In addition, in the resin structure, the matrix resin is a solidified material. The matrix resin as a solidified material is a resin that is solidified by chemical reaction or without chemical reaction, and can include, for example, a resin that is solidified by a curing reaction, a resin that is solidified by drying, a thermoplastic resin that is solidified by cooling, etc. The resin structure obtained using the above-mentioned resin composition contains a solidified material of a resin obtained by solidification using a curing agent, a polymerization initiator or a catalyst as required as a matrix resin. In this case, the matrix resin may contain a curing agent, etc. The resin structure obtained by melt-kneading the hollow particles of the present invention and a thermoplastic resin and molding contains a solidified material formed by cooling and solidifying a thermoplastic resin as a matrix resin.

[0347] The resin structure obtained using the resin composition of the present invention can be obtained, for example, by curing the curable resin, that is, by a method comprising the steps of preparing a resin composition containing the hollow particles of the present invention, a matrix resin and a curing agent, and curing the resin composition.

[0348] The curing method of the curable resin is not particularly limited, and examples thereof include heating, light irradiation such as ultraviolet rays or electron beams, etc. Alternatively, in the case of a curable resin that cures at room temperature by adding a catalyst, the resin may be cured by adding a catalyst and mixing at room temperature.

[0349] The curing agent (crosslinking agent) or catalyst for curing the matrix resin can be appropriately selected from known ones according to the type of the matrix resin, and is not particularly limited.

[0350] Examples of curing agents for epoxy resins include amines, acid anhydrides, imidazoles, thiols, phenols, naphthols, benzoxazines, cyanates, and carbodiimides. From the viewpoint of easily improving the adhesion between the epoxy resin as a matrix resin and the hollow particles of the present invention, at least one selected from amines, acid anhydrides, and imidazoles is particularly preferred.

[0351] Examples of the amines include tris(dimethylaminomethyl)phenol, diazabicycloundecene, diazabicyclononene, piperidine, N,N-dimethylpiperazine, triethylenediamine, and benzylmethylamine.

[0352] Examples of the acid anhydrides include phthalic anhydride, trimellitic anhydride, maleic anhydride, ethylene glycol ditrimellitic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylbutenyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, succinic anhydride, and methylcyclohexene dicarboxylic anhydride.

[0353] Examples of the imidazoles include 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and 1-benzyl-2-methylimidazole.

[0354] These curing agents can be used alone or in combination of two or more.

[0355] The content of the curing agent is appropriately adjusted according to the type of the matrix resin and is not particularly limited. For example, it can be 5 to 120 parts by mass based on 100 parts by mass of the resin (main agent).

[0356] When curing the resin composition, for example, the resin composition may be applied to a support, dried as necessary, and then cured under curing conditions.

[0357] Examples of the material of the support include resins such as polyethylene terephthalate and polyethylene naphthalate, and metals such as copper, aluminum, nickel, chromium, gold, and silver. A release agent may be applied to the surface of the support.

[0358] As a method for applying the resin composition, a known method can be used, and examples thereof include dip coating, roll coating, curtain coating, die coating, slit coating, and gravure coating.

[0359] When the resin composition contains a solvent, it is preferred to dry the resin composition of the present invention after the above-mentioned coating. From the viewpoint of removing the solvent while the resin composition is in an uncured or semi-cured state, the drying temperature is preferably a temperature at which the resin composition does not cure, usually 20°C or more and 200°C or less, preferably 30°C or more and 150°C or less. In addition, the drying time is usually 30 seconds or more and 1 hour or less, preferably 1 minute or more and 30 minutes or less.

[0360] The temperature when the resin composition is cured can be appropriately adjusted according to the type of the matrix resin and is not particularly limited. In the case of a thermosetting resin, it is usually 30°C to 400°C, preferably 70°C to 300°C, and more preferably 100°C to 200°C. The heating method is not particularly limited, and can be performed, for example, using an electric oven.

[0361] Furthermore, the curing time is usually 5 minutes to 5 hours, preferably 30 minutes to 3 hours.

[0362] In the resin structure of the present invention obtained by melt-kneading and molding the hollow particles of the present invention and a thermoplastic resin, a known thermoplastic resin can be used as the thermoplastic resin without particular limitation. For example, the same thermoplastic resin as the thermoplastic resin that can be used for the resin composition of the present invention can be cited. The thermoplastic resin can be used alone or in combination of two or more.

[0363] The temperature during the melt kneading is not particularly limited as long as it is a temperature at which the thermoplastic resin used can be melted. From the viewpoint of easily exerting the effect of the hollow particles of the present invention, it may be 150° C. or higher, and from the viewpoint of suppressing the breakage of the hollow particles, it is preferably 300° C. or lower.

[0364] The kneading can be performed by a known method without particular limitation, and can be performed using a kneading device such as a single-screw kneading machine or a double-screw kneading machine.

[0365] The molding method is not particularly limited, and for example, a known molding method such as extrusion molding, injection molding, press molding, etc. can be adopted.

[0366] In the resin structure of the present invention, the content of the matrix resin contained in the resin structure is not particularly limited. From the viewpoint of suppressing the reduction of the physical properties of the resin structure and improving the mechanical strength, it is preferably 30 volume % or more, more preferably 40 volume % or more. From the viewpoint of fully containing hollow particles, it is preferably 90 volume % or less, more preferably 80 volume % or less.

[0367] The content of the hollow particles contained in the resin structure of the present invention is not particularly limited, and as a lower limit, it is preferably 10% by volume or more, more preferably 20% by volume or more, and as an upper limit, it is preferably 70% by volume or less, more preferably 60% by volume or less. When the content of the hollow particles is above the above lower limit, the light weight and heat insulation effects of the resin structure brought by the hollow particles are excellent. When the content of the hollow particles is below the above upper limit, the matrix resin can be fully contained in the resin structure, so that the reduction of the physical properties of the resin structure can be suppressed, and the mechanical strength can be improved.

[0368] The resin structure of the present invention may further contain additives as necessary. As the additives, the additives that can be used for the resin composition of the present invention described above can be used in the same manner.

[0369] Furthermore, the resin structure of the present invention may be a resin structure containing organic or inorganic reinforcing fibers such as carbon fibers, glass fibers, aramid fibers, polyethylene fibers, cellulose nanofibers, and liquid crystal polymer (LCP) fibers.

[0370] The shape of the resin structure is not particularly limited, and can be made into various shapes that can be molded, such as sheet, film or plate. When the resin structure includes fibers, the fibers in the resin structure can be non-woven. In addition, the resin structure of the present invention can be a structure formed by adding hollow particles of the present invention to fiber-reinforced plastics.

[0371] As the use of the resin composition of the present invention and the resin structure of the present invention, for example, the use of the resin composition or the resin structure in the use of the hollow particles of the present invention can be cited. Specifically, for example, various components used in various fields such as automobiles, electrical, electronic, construction, aviation, and aerospace, food containers, sports shoes, sandals and other footwear, home appliance parts, bicycle parts, stationery, tools, 3D printer filaments, buoyancy materials such as composite foam, etc. can be cited.

[0372] Example

[0373] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, parts and % are based on mass unless otherwise specified.

[0374] [Example 1]

[0375] (1) Mixed solution preparation process

[0376] First, mix the following materials to prepare an oil phase.

[0377] 1,1-(bisacryloyloxymethyl)ethyl isocyanate 36.4 parts

[0378] Pentaerythritol (solubility in water at 15°C: 56 g / L, molecular weight: 136.15) 9.1 parts

[0379] 1.2 parts of diethyl peroxy tert-butyl acetate (oil-soluble polymerization initiator)

[0380] Hydrophobic solvent (cyclohexane) 54.5 parts

[0381] On the other hand, in a stirring tank, at room temperature, to an aqueous solution obtained by dissolving 7.83 parts of magnesium chloride (water-soluble multivalent metal salt) in 225 parts of ion exchange water, an aqueous solution obtained by dissolving 5.49 parts of sodium hydroxide (alkali metal hydroxide) in 55 parts of ion exchange water was slowly added under stirring to prepare a magnesium hydroxide colloid (a metal hydroxide colloid that is sparingly soluble in water) dispersion (4 parts of magnesium hydroxide) to prepare an aqueous phase.

[0382] A mixed solution is prepared by mixing the obtained aqueous phase with the oil phase.

[0383] (2) Suspension process

[0384] The mixed solution obtained in the mixed solution preparation step is passed through a disperser (product name: Homomixer, manufactured by Plemix Co., Ltd.) and stirred at a rotation speed of 4000 rpm for 1 minute to suspend it, thereby preparing a suspension in which droplets of the shell raw material composition containing a hydrophobic solvent are dispersed in water.

[0385] (3) Polymerization process

[0386] The suspension obtained in the above suspension step was stirred at 89° C. for 7 hours under a nitrogen atmosphere to perform a polymerization reaction, thereby obtaining a precursor composition in which precursor particles containing a hydrophobic solvent were dispersed in water.

[0387] (4) Cleaning process and solid-liquid separation process

[0388] The precursor composition was washed with dilute sulfuric acid (23°C, 10 minutes) to a pH of 5.5 or less. Then, after filtering and separating the water, 200 parts of ion exchange water were newly added for re-slurrying, and water washing treatment (washing, filtering, dehydration) was repeated several times at room temperature (23°C), and filtered and separated to obtain a solid component. The obtained solid component was dried at 40°C in a dryer to obtain precursor particles containing a hydrophobic solvent.

[0389] (5) Solvent Removal Process

[0390] The precursor particles obtained in the solid-liquid separation step were heat-treated in a vacuum dryer at 200° C. in a nitrogen atmosphere for 12 hours to remove the hydrophobic solvent contained in the particles, thereby obtaining hollow particles of Example 1.

[0391] [Examples 2 to 12, Comparative Examples 3 and 4]

[0392] In the above-mentioned "(1) mixed liquid preparation step" in Example 1, the type and amount of the shell raw material added to the oil phase, and at least one of the added amounts of the hydrophobic solvent and the polymerization initiator are changed according to Table 1 or Table 2. Except for this, the hollow particles of Examples 2 to 12 and Comparative Examples 3 and 4 are obtained by the same steps as Example 1.

[0393] In addition, the details of the materials used in Examples 2 to 12 and Comparative Examples 3 and 4 are as follows.

[0394] Hexamethylenediamine: Solubility in water at 15°C: 500 g / L, molecular weight: 116.20

[0395] Acrylic polymer polyol: product name ARUFON (registered trademark) UH-2000, manufactured by Toagosei Co., Ltd., Mw 11000

[0396] EBECRYL4738: Product name: EBECRYL 4738, manufactured by Daicel-Allnex Co., Ltd., urethane acrylate oligomer

[0397] ·2-Hydroxy-1,3-dimethacryloyloxypropane: molecular weight 228.24

[0398] EGDMA: Ethylene glycol dimethacrylate

[0399] ·Polyester polyol: Product name: Poly-Lite OD-X-2420, manufactured by DIC Corporation, molecular weight: 2000

[0400] · Polyether polyol A: Product name: ADEKA POLYETHER P series, manufactured by ADEKA Co., Ltd., composition: PG·PO series (polyether polyol obtained by addition polymerization of propylene glycol and propylene oxide)

[0401] Polyvalent epoxy: Product name: DENACOL EX-201, manufactured by Nagase ChemteX Co., Ltd., Compound name: resorcinol diglycidyl ether, Molecular weight: 222.24

[0402] Ethylene glycol: mixed with water, molecular weight 62.07

[0403] [Comparative Example 1]

[0404] Comparative Example 1 corresponds to Example 1 of Patent Document 1.

[0405] First, mix the following materials to prepare an oil phase.

[0406] Aromatic polyisocyanate (product name: BURNOCK (registered trademark) D-750, manufactured by DIC Corporation, toluene diisocyanate trimethylolpropane adduct) 49.5 parts by mass

[0407] Polyether polyol B (product name: ADEKA POLYETHER EPD-300, manufactured by ADEKA Co., Ltd., compound name: N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine) 0.5 parts by mass

[0408] Limonene 50 parts by mass

[0409] 100 parts by mass of the oil phase obtained above was added to 100 parts by mass of a 5% aqueous solution of polyvinyl alcohol to prepare a mixed solution. The obtained mixed solution was stirred at a rotation speed of 1400 rpm and heated to 70° C., thereby obtaining a precursor composition in which the precursor particles containing the hydrophobic solvent were dispersed in water. The precursor particles were powdered by spray drying, and then heated in a drying oven at 200° C. for 3 hours to remove the limonene contained in the particles, thereby obtaining hollow particles of Comparative Example 1.

[0410] [Comparative Example 2]

[0411] Comparative Example 2 corresponds to Example 1 of Patent Document 3.

[0412] First, mix the following materials to prepare an oil phase.

[0413] Trimethylolpropane triacrylate 19 parts by mass

[0414] Methacrylic acid 1 part by mass

[0415] Polymerization initiator (2,2-azobis(2-methylbutyronitrile)) 0.4 parts by mass

[0416] Toluene 56 parts by mass

[0417] Hexane 24 parts by mass

[0418] The oil phase obtained above is added to an aqueous solution obtained by dissolving 5 parts by mass of polyvinyl alcohol in 400 parts by mass of distilled water to prepare a mixed solution. The obtained mixed solution is stirred at a rotation speed of 1000 rpm and heated to 70°C, thereby obtaining a precursor composition obtained by dispersing precursor particles containing a hydrophobic solvent in water. The obtained precursor composition is filtered, and water is separated to obtain precursor particles. The obtained precursor particles are repeatedly washed with water (washing, filtering and dehydrating) for several times, and then dried at 40°C in a dryer to obtain precursor particles containing a hydrophobic solvent. Next, the hydrophobic solvent contained in the particles is removed by heating in a vacuum dryer at 200°C and a nitrogen atmosphere for 12 hours to obtain hollow particles of Comparative Example 2.

[0419] [evaluate]

[0420] The following measurements and evaluations were performed on the hollow particles obtained in each Example and each Comparative Example.

[0421] <Measurement or Evaluation of Hollow Particles>

[0422] 1. Determination of IR spectrum

[0423] The hollow particles were measured by ATR-FTIR to obtain an infrared absorption spectrum. Based on the obtained infrared absorption spectrum, the 1500-1550 cm -1 The maximum peak absorbance A1 in the range of 1700-1750cm -1 The absorbance ratio (A1 / A2) of the maximum peak in the range of A2 is calculated. In addition, the infrared absorption spectrum is measured by connecting an ATR accessory (product name: Nicolet iS5 spectrophotometer iD5ATR accessory, manufactured by Thermo Fisher Scientific) to a Fourier transform infrared spectrometer (FT-IR) (product name: Nicolet iS5 FT-IR spectrometer, manufactured by Thermo Fisher Scientific). The absorbance ratio (A1 / A2) is calculated as the peak top intensity ratio.

[0424] The measurement conditions of ATR-FTIR are as follows.

[0425] <Measurement Conditions>

[0426] High refractive index seed crystal: Diamond with ZnSe lens

[0427] Incident angle: 42°±1°

[0428] Measuring area: 4000cm -1 ~600cm -1

[0429] Dependence of mantissa on measured depth: Uncorrected

[0430] Reflection times: 1

[0431] Detector: DTGS

[0432] KBr resolution: 4cm -1

[0433] Cumulative times: 16 times

[0434] Others: The infrared absorption spectrum is measured under the above conditions without contact with the sample, and the measured spectrum is used as the background. When measuring the sample, the measured data is processed in a way that the background does not affect the measured spectrum. In the ATR method, the intensity of the infrared absorption spectrum measured varies depending on the degree of close contact between the sample and the high refractive index crystal. Therefore, the maximum load applied by the ATR accessory is applied to make the close contact roughly uniform for measurement.

[0435] 2. Porosity

[0436] 2-1. Determination of apparent density of hollow particles

[0437] First, in a volume of 100cm 3 Fill the volumetric flask to about 30 cm 3 The mass of the hollow particles is accurately weighed. Next, the volumetric flask filled with the hollow particles is accurately filled to the mark with isopropyl alcohol, taking care not to mix in bubbles. The mass of the isopropyl alcohol added to the volumetric flask is accurately weighed, and the apparent density D of the hollow particles is calculated based on the following formula (I): 1 (g / cm 3 ).

[0438] Formula (I)

[0439] Apparent density D 1 = [mass of hollow particles] / (100 - [mass of isopropyl alcohol] / [specific gravity of isopropyl alcohol at the measurement temperature])

[0440] 2-2. Determination of true density of hollow particles

[0441] After the hollow particles are crushed in advance, the volume is 100cm 3 A volumetric flask is filled with about 10 g of hollow particle fragments, and the mass of the filled fragments is accurately weighed.

[0442] Then, isopropyl alcohol was added to the volumetric flask in the same manner as in the above-mentioned measurement of apparent density, the mass of isopropyl alcohol was accurately weighed, and the true density D of the hollow particles was calculated based on the following formula (II): 0 (g / cm 3 ).

[0443] Formula (II)

[0444] True density D 0 = [mass of hollow particle fragments] / (100 - [mass of isopropyl alcohol] / [specific gravity of isopropyl alcohol at the measurement temperature])

[0445] 2-3. Calculation of porosity

[0446] According to the apparent density D of the hollow particles 1 and true density D 0 , the porosity of the hollow particles was calculated based on the following formula (III).

[0447] Formula (III)

[0448] Porosity (%) = 100 - (apparent density D 1 / True density D 0 )×100

[0449] 3. Micro compression fracture strength

[0450] The micro compression fracture strength of the hollow particles was measured at a measurement temperature of 23° C. or 150° C. under the following conditions using a micro compression tester (model: MCT-510) manufactured by Shimadzu Corporation in accordance with JIS R1639-5.

[0451] <Measurement Conditions>

[0452] Maximum test force: 2.000mN

[0453] Load speed: 0.0466mN / s

[0454] Humidity: 45±5%RH

[0455] Indenter shape: frustum (flat indenter)

[0456] Indenter tip size: φ200μm

[0457] Indenter material: Diamond

[0458] Number of particles measured: 10

[0459] 4. Average roundness

[0460] 0.10 to 0.12 g of the hollow particles were placed in an aqueous solution of sodium linear alkylbenzene sulfonate (concentration 0.3%) to obtain a mixed solution, and the obtained mixed solution was dispersed for 5 minutes using an ultrasonic cleaner to prepare a measurement sample. The circularity of 1000 to 3000 particles contained in the measurement sample was measured under the following measurement conditions using a flow particle image measuring device (product name: IF-3200, manufactured by Jasco International Co., Ltd.), and the arithmetic mean was taken as the average circularity.

[0461] (Measurement conditions)

[0462] Flow cell spacer thickness: 50 μm

[0463] Telecentric zoom lens magnification: 4.5x

[0464] Total magnification: 9.0 times

[0465] Measurement volume: 0.5mL

[0466] Image resolution: 0.185μm / pixel

[0467] Detection algorithm: Ghost detection

[0468] Threshold: 15%

[0469] 5. Particle size and particle size distribution

[0470] The volume-based particle size distribution of the hollow particles was obtained using a particle size distribution measuring instrument based on the Coulter counter method (product name: Multisizer 4e, manufactured by Beckman Coulter Inc.), the volume-based cumulative 50% particle size D50 and the volume-based cumulative 90% particle size D90 were determined, and the ratio of D90 to D50 (D90 / D50) was calculated.

[0471] The measurement conditions are as follows: pore size: 50 μm, dispersion medium: ISOTON II (product name), concentration 10%, and number of particles to be measured: 100,000. Specifically, 0.2 g of a particle sample is placed in a beaker, and a surfactant aqueous solution (product name DRIWEL, manufactured by Fujifilm Corporation) is added thereto as a dispersant. Further, 2 ml of the dispersion medium is added thereto to wet the particles, and then 10 ml of the dispersion medium is added, and the particles are dispersed for 1 minute using an ultrasonic disperser, and then the particle size distribution is measured using the above-mentioned particle size distribution measuring machine.

[0472] 6. Thermal decomposition temperature

[0473] The thermal decomposition temperature of the hollow particles was measured using a differential thermal and thermogravimetric simultaneous measurement device (product name: TG / DTA6200, automatic sampler: AST-2, manufactured by Seiko Epson Corporation). The sampling method and temperature conditions were as follows. 10.5±0.5 mg of hollow particles were filled at the bottom of a platinum measurement container without gaps as a sample for measurement. The sample was heated from 30°C to 500°C at a nitrogen flow rate of 230 mL / min and a heating rate of 10°C / min to obtain a TG / DTA curve. The analytical software included with the device was used to calculate the temperature at which the weight of the hollow particles decreased by 5% as the thermal decomposition temperature.

[0474] 7. Porosity maintenance rate after injection molding

[0475] 0.2 g of hollow particles and 0.8 g of polypropylene (product name: NOVATEC PP MA1B, manufactured by Japan Polypropylene Co., Ltd.) are melted and mixed on a hot plate heated to above 200°C to obtain a mixture. The obtained mixture is placed in a Φ14 mm hot press metal mold (manufactured by Aswan Co., Ltd.), and the metal mold is placed in a 230°C dryer and heated for 15 minutes. The removed metal mold is set in a hot press (model: H300-15, manufactured by Aswan Co., Ltd.) set at 90°C, and a 90°C barrel is placed in the mold. At the moment when the surface temperature of the metal mold drops to 130°C, a pressing pressure of 30 MPa is applied to produce a resin structure. At this time, the barrel pressure of the press is set to 2 MPa. According to the addition amount of hollow particles and the apparent density D 1 , the amount and specific gravity of the matrix resin added, and the specific gravity of the obtained resin structure, the pore maintenance rate (%) of the hollow particles after injection molding is calculated. The higher the pore maintenance rate of the hollow particles after injection molding, the better the pressure resistance at high temperature can be evaluated.

[0476] [Table 1]

[0477]

[0478] [Table 2]

[0479] Table 2

[0480]

[0481] In addition, for the hollow particles obtained in each embodiment and each comparative example, based on the SEM observation results and the porosity value, it was confirmed that all the hollow particles were spherical and had only one hollow part. Among the hollow particles obtained in each embodiment, the number ratio of particles having only one hollow part was 90% or more.

[0482] [Investigation]

[0483] In Comparative Example 1, an acrylic acid-based high molecular surfactant was used as the active hydrogen compound, but the polymerization reaction of the acryloyl group was not carried out. Therefore, in the hollow particles obtained in Comparative Example 1, the resin forming the shell contained a urethane bond but did not contain a structure formed by the polymerization of (meth)acryloyl groups. As a result, the hollow particles obtained in Comparative Example 1 had a low thermal decomposition temperature and poor heat resistance. The micro-compression fracture strength at 150°C was significantly lower than the micro-compression fracture strength at 23°C, the pore maintenance rate after PP injection molding was also low, and the pressure resistance was easily reduced at high temperatures.

[0484] In the hollow particles obtained in Comparative Example 2, the resin forming the shell does not contain any of the urethane bonds and urea bonds, although it contains a structure formed by polymerization of (meth)acryloyl groups. In addition, the D90 / D50 of the hollow particles obtained in Comparative Example 2 is greater than 1.70. As a result, the hollow particles obtained in Comparative Example 2 have a low thermal decomposition temperature, poor heat resistance, low micro-compression fracture strength at 23°C, poor pressure resistance, and significantly lower micro-compression fracture strength at 150°C than the micro-compression fracture strength at 23°C. The porosity maintenance rate after PP injection molding is also low, and the pressure resistance is easily reduced at high temperatures.

[0485] In the hollow particles obtained in Comparative Example 3, although the resin forming the shell contains a structure formed by polymerization of (meth)acryloyl groups and a carbamate bond, the average circularity is less than 0.90. The hollow particles obtained in Comparative Example 3 have a low thermal decomposition temperature, poor heat resistance, low micro-compression fracture strength at 23°C, poor pressure resistance, and a significantly lower micro-compression fracture strength at 150°C than the micro-compression fracture strength at 23°C. The porosity maintenance rate after PP injection molding is also low, and the pressure resistance is easily reduced at high temperatures. It can be inferred that in Comparative Example 3, since the polymerization reaction in the shell was not fully carried out, the particles were deformed and the average circularity was less than 0.90. It can be inferred that the polymerization reaction in the shell of the hollow particles of Comparative Example 3 was not fully carried out, and thus the cross-linking density of the shell was low, and therefore, the thermal decomposition temperature was low, and the pressure resistance was easily reduced at high temperatures.

[0486] In the hollow particles obtained in Comparative Example 4, although the resin forming the shell contains a structure formed by polymerization of (meth)acryloyl groups and urethane bonds, D90 / D50 is greater than 1.70, and the amount of coarse powder is large. The hollow particles obtained in Comparative Example 4 have a low thermal decomposition temperature, poor heat resistance, low micro-compression fracture strength at 23°C, poor pressure resistance, and significantly lower micro-compression fracture strength at 150°C compared to the micro-compression fracture strength at 23°C. The porosity maintenance rate after PP injection molding is also low, and the pressure resistance is easily reduced at high temperatures. It can be inferred that in Comparative Example 4, the reaction between the particles proceeds to produce coarse particles, so that D90 / D50 is greater than 1.70. It can be inferred that the hollow particles in Comparative Example 4 do not fully proceed due to the reaction between the particles, so that the crosslinking density of the shell is low, and therefore, the thermal decomposition temperature is low, and the pressure resistance is easily reduced at high temperatures.

[0487] In contrast, in the hollow particles obtained in each example, the resin forming the shell includes a structure formed by polymerizing (meth)acryloyl groups and at least one selected from urethane bonds and urea bonds, and the average circularity is 0.90 or more, and D90 / D50 is 1.70 or less. Therefore, the thermal decomposition temperature is high, the heat resistance is excellent, the micro-compression fracture strength at 23°C is high, the pressure resistance is excellent, the reduction of the micro-compression fracture strength at 150°C is suppressed compared with the micro-compression fracture strength at 23°C, the pore maintenance rate after PP injection molding is also high, and the reduction of pressure resistance at high temperature is suppressed. In addition, the shells of the hollow particles obtained in Examples 1, 3 to 12 include a structure formed by polymerizing (meth)acryloyl groups and urethane bonds, and the shells of the hollow particles obtained in Example 2 include a structure formed by polymerizing acryloyl groups and urea bonds.

[0488] In addition, in the hollow particles of Examples 1 to 8 and 10 to 12 in which the resin forming the shell is a polyurethane-acrylic hybrid polymer, the thermal decomposition temperature or the pore maintenance rate after PP injection molding is particularly high, and the heat resistance or pressure resistance at high temperatures is excellent.

[0489] In addition, in the hollow particles of Examples 1 to 3 using a mixture of an isocyanate group-containing multifunctional (meth)acrylate and at least one active hydrogen compound selected from polyamines, aliphatic polyols and (meth)acrylic polymer polyols as a shell raw material, and the hollow particles of Example 6 using a mixture of a polyisocyanate and a hydroxyl group-containing (meth)acrylate as a shell raw material, the micro-compression fracture strength at 150°C is 15.0 MPa or more, the pore maintenance rate after PP injection molding is 90% or more, and the pressure resistance at high temperature is particularly excellent.

[0490] Description of Reference Numerals

[0491] 1: Water-based medium;

[0492] 2: Low polarity materials;

[0493] 3: droplets of shell raw material composition;

[0494] 4a: hydrophobic solvent;

[0495] 4b: Materials other than hydrophobic solvents;

[0496] 5: Precursor particles;

[0497] 6: Shell;

[0498] 7: hollow part;

[0499] 10: Hollow particles whose hollow parts are filled with gas.

Claims

1. A hollow particle having a shell containing a resin and a hollow portion surrounded by the shell, The resin comprises a structure formed by polymerization of (meth)acryloyl groups and at least one selected from urethane bonds and urea bonds, The average circularity of the hollow particles is greater than 0.90, When the volume-based cumulative 50% particle size of the hollow particles is D50 and the volume-based cumulative 90% particle size of the hollow particles is D90, a ratio of D90 to D50 (D90 / D50) is 1.70 or less, The breaking strength of the hollow particles when compressed using a micro compression tester at 150° C., a maximum crushing test force of 2000 mN, and a load speed of 0.0466 mN / s is 5.0 MPa or more.

2. The hollow particles according to claim 1, wherein In the infrared absorption spectrum obtained by measuring the hollow particles by ATR-FTIR, 1500-1550cm -1 The maximum peak absorbance A1 in the range of 1700-1750cm -1 The ratio (A1 / A2) of the absorbance A2 of the maximum peak in the range is greater than or equal to 0.1 and less than or equal to 0.

5.

3. The hollow particles according to claim 1 or 2, wherein The urea bond is a urea bond generated by a reaction between a polyamine and an isocyanate group-containing compound.

4. The hollow particles according to claim 1 or 2, wherein The urethane bond is a urethane bond generated by the reaction of at least one active hydrogen compound selected from a hydroxyl group-containing compound and an epoxy group-containing compound with an isocyanate group-containing compound. The hydroxyl-containing compound is at least one selected from polyester polyols, polyether polyols, aliphatic polyols, (meth)acrylic polymer polyols and hydroxyl-containing (meth)acrylates, and the epoxy-containing compound is a polycyclic epoxy compound.

5. The hollow particles according to claim 1 or 2, wherein The hollow particles have a porosity of 60% or more and 85% or less.

6. A method for producing hollow particles, which is a method for producing the hollow particles according to any one of claims 1 to 5, comprising: A step of preparing a mixed solution comprising a shell raw material, a hydrophobic solvent, a dispersion stabilizer and an aqueous medium; A step of suspending the mixed solution to prepare a suspension in which droplets of a shell raw material composition containing the shell raw material and the hydrophobic solvent are dispersed in the aqueous medium; a step of forming precursor particles by polymerizing the shell raw material, the precursor particles having a shell containing a resin and a hollow portion surrounded by the shell and filled with the hydrophobic solvent; and a step of removing the hydrophobic solvent from the precursor particles, The shell raw material comprises at least one selected from the following (i), (ii) and (iii): (i) a mixture of compounds, which is a mixture of an isocyanate group-containing compound and an active hydrogen compound, at least one of the isocyanate group-containing compound and the active hydrogen compound contains a (meth)acryloyl group, and the active hydrogen compound is at least one selected from an amino group-containing compound, a hydroxyl group-containing compound, and an epoxy group-containing compound, The mixture of the compounds satisfies at least one of the following: the isocyanate group-containing compound contains two or more isocyanate groups in one molecule, or the active hydrogen compound contains two or more at least one selected from amino, hydroxyl and epoxy groups in one molecule; (ii) at least one selected from urethane bond-containing (meth)acrylates and urea bond-containing (meth)acrylates; as well as (iii) a mixture of compounds, which is a mixture of an isocyanate group-containing compound, an active hydrogen compound and a (meth)acryloyl group-containing compound, wherein the active hydrogen compound is at least one selected from an amino group-containing compound, a hydroxyl group-containing compound and an epoxy group-containing compound, In the polymerization of the shell raw material, at least one of a reaction between an isocyanate group and at least one selected from an amino group, a hydroxyl group, and an epoxy group, and a radical polymerization reaction of a (meth)acryloyl group proceeds. 7 . A resin composition comprising a matrix resin and the hollow particles according to claim 1 .

8. A resin structure comprising a matrix resin and the hollow particles according to any one of claims 1 to 5, The content of the hollow particles is 10% by volume or more and 70% by volume or less.

9. The resin structure according to claim 8, wherein The matrix resin is an epoxy resin.

10. A method for manufacturing a resin structure, comprising: A process for preparing a resin composition comprising the hollow particles according to any one of claims 1 to 5, a matrix resin and a curing agent; as well as a step of curing the resin composition, The base resin comprises an epoxy resin, The curing agent comprises at least one selected from amines, acid anhydrides and imidazoles.

Citation Information

Patent Citations

  • Resin particle

    JP2020033503A

  • Hollow particles and method for producing the same, resin composition containing hollow particles and method for producing the same

    JP2022117594A

  • Method for producing hollow particles, method for producing pore-making material, method for producing particles for cosmetics, and method for producing weight-reducing material

    WO2019181988A1